Coating agent for forming solid lubricating film, method for producing said coating agent, method for repair well pipe, method for improving lubricance of well pipe,
By using reagents for coating the water-based polymer matrix without MoS2 in the lubrication of oil well tube threads, graphite and metal soap are added as solid lubricants, and the addition of trace alkaline soaps is solved, and the problems of mild burns and early drying are achieved, achieving efficient lubrication and environmentally friendly results.
Patent Information
- Application Number
- CN202380060476.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-08-14
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art has a tendency to be mildly burned in the lubrication of oil well pipe threads, and the use of lubricants containing MoS2 may cause thread rupture, and it is difficult to achieve early drying of the dry solid lubricating membrane in a well site environment where smoking is strictly prohibited.
A coating reagent without MoS2 was designed, using aqueous polymers as substrates, graphite and metal soap as solid lubricants, and early drying and high lubricity were achieved by adjusting the composition and adding trace amounts of alkaline soap.
In the well site environment where stoke fires are strictly prohibited, efficient lubrication of oil well pipe threads and repair of mild burns are achieved, avoiding the rupture problems caused by MoS2, and improving lubrication performance and environmental friendliness.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention is a coating agent suitable for forming a solid lubricating film, and a technique for repairing and improving lubrication performance of oil well pipe threads using the coating agent. That is, the present invention is a technique for lubricating the metal surface of a metal part such as an oil well pipe thread using a solid lubricating film.
[0002] The present invention is used, for example, when it is necessary to further improve the lubricity of an existing solid lubricating film. That is, the present invention also includes coating on an existing solid lubricating film for the purpose of improving lubricity and avoiding burning as a preventive measure. The present invention also includes the case where lubrication is achieved only by the solid lubricating film of the present invention.
[0003] In addition, the present invention relates to lubrication of oil well pipe threaded joints, for example, and is used when only the threaded portion of the threaded portion and the sealing portion constituting the oil well pipe thread is slightly burned. For example, the present invention relates to an agent, which is applied for the purpose of grinding the burned portion with a grinder, sandpaper, file, etc. for maintenance and local repair of the area on the spot. Local repair is also called repair. Background Art
[0004] Conventionally, for oil well pipes used in oil / gas excavation sites and production, wet lubricating compounds are used to lubricate the threaded parts (joint parts) during tightening and loosening. Moreover, lubrication using lubricating compounds is still the mainstream.
[0005] For example, when the oil well pipe is made of carbon steel, a phosphoric acid Mn chemical conversion treatment film is formed on the thread surface as a base. In addition, when the oil well pipe is made of stainless steel / high alloy, an electroplated film represented by a Cu plating layer is applied on the thread surface as a base on the sleeve thread (internal thread) side. Then, a lubricating compound is applied to either or both of the sleeve thread and the pin thread to impart lubricity.
[0006] Lubricating compounds have always been compounds composed of greases and the like to which heavy metals such as Pb, Zn, and graphite are added. Currently, compounds that have been free of such heavy metals are also available and used in order to cope with the environment. In addition, although not yet mainstream, lubrication technology using dry solid lubricating films is also being used.
[0007] Wet compounds form a wet lubricating film. In contrast, lubrication technology using solid lubricating films is called dry technology or grease-free technology. Lubrication technology using solid lubricating films is becoming one of the important technologies that can achieve lubrication of oil well pipes used in oil / gas excavation sites and production.
[0008] However, no matter how the lubrication technology is improved, there will be a certain amount of poor tightening, although it is small. Moreover, as a cause of poor tightening, for example, if there is burning or damage in the sealing part, the sleeve thread and the pin thread will be unqualified. The unqualified sleeve thread will be discarded. In addition, for the unqualified pin thread with a slight damage in the sealing part among the actual length pin threads, in most cases, only the pin thread part is cut off and the thread is cut again. In the most serious case, when the pin thread and the sleeve thread are fiercely meshed and cannot be separated, both threads are subject to disposal.
[0009] Here, the actual length of the pin thread in this specification means more than 10 m.
[0010] However, when the sealing part is in a sound state and only the thread area is slightly damaged, repair (local repair) is performed. For example, at the well site, the slightly burned part of the thread area of the sleeve thread and the thread area of the pin thread is repaired. That is, the damaged part is taken as the center and its surroundings are ground with a grinder, sandpaper, file, etc. for maintenance. During this maintenance, the base film such as the Mn phosphate chemical conversion treatment and the electroplating treatment layer of the base that serves as the lubrication target disappears due to the maintenance. Therefore, in the past, commercially available lubricating pastes, lubricating sprays, etc. were applied to repair the sealing part to maintain lubrication.
[0011] Such a situation that requires repair (local repair) at the well site sometimes occurs naturally at a certain ratio. In addition, in the case of severe burns, there are also parts where the metal part of the part is ground away due to maintenance. Therefore, a repair agent is preferably used to fill the ground part.
[0012] In the case of such repairs, it is almost impossible to deal with it by simply applying the conventional lubricating compound, that is, a compound with heavy metal groups such as Pb, Zn, and graphite. In the repair, a commercially available repair product group (repairing agent) of anti-scaling spray, paste, and compound is used. The field of anti-scaling lubricants covers a wide range. For example, there are many types, ranging from a composition of only mineral oil, to a composition in which metal powder (Zn series, Ni series) is dispersed in mineral oil, etc., to a composition in which lubricants (graphite, MoS2, BN, PTFE, silicon) are dispersed in mineral oil, etc.
[0013] In places with severe load conditions (heavy-duty applications), such as oil well pipe thread lubrication, commercially available products with a trade name called Molykote are generally used. TM: Dow Corning, Dupont) and similar product groups. Now, Molykote itself has become a brand name. Therefore, as Molykote, it is not necessarily the substance to which MoS2 is added, but there are also products made of Zr-based, F-based, and graphite-based substances or mixtures. However, in this specification, Molykote mainly refers to substances containing MoS2. In addition, in the following description, Molykote and similar product groups are sometimes collectively referred to as Molykote.
[0014] It is also possible to lubricate the threads of oil well pipes using only anti-seize sprays or pastes other than Molykote. However, they are expensive. Therefore, it is not common to apply them at work sites near wells or to lubricate the threads of oil well pipes using them alone at the well tightening site.
[0015] The effective use of Molykote in the field of oil well pipes is usually only used in the following cases when lubrication is abnormal. That is, the general use method is to apply Molykote to the pipe when repairing the burnt part at the well site after curing it at the well site. However, Molykote is a lubricant that guarantees high lubricity, and it is not a putty-like material that fills the repaired part. Molykote is a repair material after all.
[0016] The Molykote described in this specification mainly contains MoS2 and oil-based solvents such as mineral oil (organic solvent system) to synthetic oil. That is, Molykote is composed of MoS2 dispersed and mixed in mineral oils such as white mineral oil, PAO (poly α-olefin), PAG (polyalkylene glycol), etc. Moreover, Molykote in a spray or paste form is usually applied to the repaired area. White mineral oil is baby oil, and it is a colorless liquid and non-volatile stable oil at room temperature. It should be noted that in Molykote, there are also substances that make the oil have viscosity by mixing lithium soap and calcium soap as thickeners in the mineral oil of the base substrate.
[0017] As mentioned above, the thread with burnt thread area can be used again by repairing it at the well site. In this case, Molykote is applied to the entire surface of the thread and tightened. Alternatively, in some cases, after applying only the repair amount of Molykote and letting it dry, a lubricating compound (API-Mod, etc.) is applied to the entire surface of the thread and tightened again. In this case, wait for the mineral oil to dry before using the lubricating compound.
[0018] The purpose of this repair at the well site is to maintain the sealing of the thread. It is a remedial measure for the slight burn in the thread area. However, it cannot be remedied even if the sealing part is slightly burned. In addition, in the case of insufficient lubrication predicted in advance, Molykote is sometimes used as a preventive coating to improve the lubricity by one level.
[0019] On the other hand, Molykote containing MoS2 is also pointed out to have problems. That is, it is pointed out that when laying the thread, if there is no interval from the laying date, there is a high concern that the thread itself, that is, the coupling, will be broken due to hydrogen embrittlement due to MoS2 in the well.
[0020] Recently, the strength and hardness of oil well pipes have gradually increased, and this concern has gradually been regarded as a problem. For example, Non-Patent Document 1 records a report that a Ni-based alloy oil well pipe cracked when a lubricant composed of a spray containing MoS2 was applied. In addition, among oil / gas engineers, there is also a thought that MoS2 turns into H2S, resulting in increased concerns about hydrogen embrittlement. Therefore, for reagents used for the purpose of repairing well sites, there is a high demand to avoid the use of Molykote containing MoS2.
[0021] In addition, in oil well pipe thread lubrication, not only the conventional method of using a wet compound for lubrication, but also the new technology of "technology using a solid lubricating film" may require repair at the well site as described above.
[0022] According to the investigation by the present inventors, it has been found that, unlike the case of using a lubricating compound, lubrication using a solid lubricating film tends to cause mild seizures.
[0023] The lubricating compound is in the form of a viscous liquid paste. Therefore, the compound moves in conjunction with tightening and loosening. On the other hand, the solid lubricating film is not like this, and is inevitably slightly ground due to tightening and loosening. Moreover, it cannot be expected that the fragments and peeling pieces from the solid lubricating film itself will always move in conjunction with tightening and loosening. In the case where the secondary products of these fragments and the like are clogged in the thread gap, burns develop. Therefore, repairs at the well site are still valued in lubrication using solid lubricating films.
[0024] Here, in the case where the thread portion of the solid lubricating film is slightly burned, it is also conceivable to use Molykote as in the past. However, there is a concern about the cracking problem that may be caused by MoS2 as described above, and there is a high demand to avoid Molykote containing MoS2.
[0025] In addition, the solid lubricating film is a dry solid lubricating film called a dry film. In the repair of a well site, if Molykote in a paste or spray form is used, there are other problems in the case of the solid lubricating film.
[0026] That is, Molykote is dissolved in solvents such as mineral oils to synthetic oils such as white oil, PAO, and PAG. Therefore, rather than saying that the film formed by Molykote is completely dry, it is better to say that most of them are slightly wet films. Therefore, Molykote does not meet the technical concept of dry solid lubricating films. Strictly speaking, Molykote does not belong to the technical category of solid lubricating films based on the premise of "drying". When Molykote is in a spray form, there are cases where it can be handled as a dry film if it is dried. However, in most cases, solid lubricating components and binder resin components are mixed in white oil-based solvents, and drying takes time. Even if you wait for a long time to dry, most of them are semi-wet and cannot reach a completely dry level.
[0027] In addition, fireworks are strictly prohibited at the well site. Dryness is a priority at the well site, and VOCs (volatile organic solvents) such as toluene, xylene, and benzene, which have low boiling points and flash points, must be avoided.
[0028] In addition, fluororesins containing PFAS dispersed in fluorinated solvents (such as HFE) have quick drying properties due to their low boiling points. Moreover, unlike conventional VOCs, these fluororesins have high flash points and do not cause fire or explosion, so they can provide safe films that can be dried early. However, based on the fact that the use of PFAS was strictly restricted in TSCA in April 2021, it can be judged that products containing PFAS are essentially unusable.
[0029] In addition to the repair at the well site, there are also the following uses. That is, there are cases where the lubricity characteristics of the existing solid lubricating film itself need to be improved by one level, rather than the local repair expected by the repair. This is a viewpoint that the previous technology of fastening the composite to the base film does not have. It should be noted that the base film is formed by chemical conversion treatment and electroplating.
[0030] As mentioned above, in the lubrication technology of oil well pipe threads, a phosphoric acid Mn chemical conversion treatment film and an electroplating film are applied as a base on the sleeve thread (internal thread) side. Then, a lubricating compound is applied in a manner that covers the lubricating surfaces of the threads to achieve lubricity. The lubricating compound is a paste with a viscous liquid, and the compound moves in conjunction with tightening and loosening. Therefore, the size of the oil well pipe is not greatly affected, and excellent lubrication can be expected.
[0031] On the other hand, the outer diameter and wall thickness of the oil well pipe are strongly affected by the solid lubricating film. In the lubrication of the solid lubricating film, lubrication is achieved while the solid lubricating film itself is gradually ground. Therefore, when the film is damaged by misalignment during tightening or when the pin thread (external thread) is initially inserted and set, the impact on the coupling thread (internal thread) is applied. As a result, there is a tendency to burn easily in the lubrication of the solid lubricating film.
[0032] In particular, in the case of large-diameter and thick-walled materials, the tightening torque value becomes larger and the weight of the pin thread also becomes heavier. Therefore, in the actual field, when tightening while hanging upright, the solid lubricating film may be completely peeled off and damaged.
[0033] In the solid lubricating film, even if the same reagent is used, the lubricating characteristics represented by the number of tightening and loosening times may be such that the performance that can be achieved with a small-diameter pin thread cannot be achieved with a large-diameter pin thread. Therefore, when repairing the solid lubricating film, a new lubricating film is formed in a manner that covers the entire existing solid lubricating film. Alternatively, a new lubricating film (lubricating auxiliary film) is used to protectively cover a locally weak portion. In this way, there is a need to improve lubrication, especially for large-diameter and thick-walled oil well pipes.
[0034] In this case, when the base film is not considered, the overall structure of the solid lubricating film is a two-layer film structure. The case of not considering the base film refers to, for example, the case of not considering the phosphoric acid chemical conversion film and the plating film.
[0035] The whole-surface two-layer film structure and local film strengthening are described in, for example, Patent Documents 1 and 2. In these Patent Documents, there are descriptions of portions that have a two-layer structure for the purpose of local strengthening, especially portions that target shoulders. That is, as portions that have a two-layer structure, examples of high hardness on the surface side (Patent Document 1) and examples of high friction coefficient (Patent Document 2) are disclosed.
[0036] There are many examples of a two-layer structure for the entire surface. For example, Patent Documents 3 and 4 can be cited. These are two-layer structures for the entire surface.
[0037] In Patent Document 3, a solid lubricating film (only a binder resin) without a solid lubricant is formed on the surface layer, and a normal solid lubricating film with a solid lubricant is formed on the lower layer. However, the two-layer structure in Patent Document 3 covers the point where the solid lubricating film becomes porous due to the addition of a solid lubricant and thus lacks rust resistance. Therefore, Patent Document 3 aims to improve corrosion resistance.
[0038] In Patent Document 4, a viscous liquid lubricating layer is formed on the lower layer, and it moves in conjunction with tightening and loosening, as in the conventional lubrication using a composite material. Thus, in Patent Document 4, the purpose is to always maintain lubrication in a self-repairing manner. In addition, in Patent Document 4, the solid lubricating film of the upper layer has the function of covering the viscous liquid lubricating layer of the lower layer. Moreover, the solid lubricating film of the upper layer is easily destroyed when extremely strong surface pressure is applied, and it becomes one with the lower layer to form a lubricating layer. In addition, in Patent Document 4, the hardness of the layer is designed so that the upper layer is hard and the lower layer is soft, and most of the lubrication function is due to these layers.
[0039] Here, as described above, further application of lubricant to the threaded portion of the oil well pipe and the addition of a lubricating film structure have the effect of repairing the well site and improving the lubrication of the oil well pipe by one level when the oil well pipe is of large diameter. At this time, it is preferred to make the reagent used universal. That is, any operation may be used in the same operation area of the well site. Therefore, it is effective to improve the user's convenience by using one reagent. Moreover, it is also effective to avoid the coexistence of two reagents and the wrong application. In the reagent design at this time, corrosion resistance can be excluded from the necessary characteristics. The required necessary characteristics are that it can be repaired at the well site, and lubricity is ensured and lubrication of the oil well pipe is improved when the oil well pipe is of large diameter.
[0040] However, no such technical concept has been found in the existing literature in the past.
[0041] In addition, as conventional techniques, there are techniques described in Patent Documents 5 to 7.
[0042] Patent Document 5 exemplifies the formation of an acrylic silicone resin on a UV-cured film, wherein the acrylic silicone resin contains a metal soap as a solid lubricant. In addition, the spray-on type of acrylic silicone resin for a lacquer base is exemplified in terms of water-based and oil-based properties, and describes that the oil-based property is preferred. In other words, the aqueous binder resin is not actively used.
[0043] Patent Document 6 describes a lubricating film having a viscous liquid or semi-solid state and a dry solid film formed thereon, wherein both films contain a solid lubricant.
[0044] Patent Document 7 cites acrylic resin as an example of a thermoplastic resin. It is described that a metal soap or wax is contained in the non-volatile component as an example. It is also described that wax is effective not only in preventing burns but also in reducing the fluidity of the lubricating film-forming composition and improving the film strength. It is also described that any of animal, plant, mineral, and synthetic waxes can be used.
[0045] In addition, as conventional techniques that are aware of actual tightening in a well, there are, for example, Patent Documents 8 and 9, and Non-Patent Document 2.
[0046] Patent Document 8 clearly states that: a vertical power tong is used, and misalignment is assumed, a 7" short pin is used, and an initial setting is tested at an angle of 6 degrees.
[0047] Here, the length of the short pin in this specification refers to the general length of the pin used in the thread test of API RP 5C5 2017. Specifically, the length is about 1 m.
[0048] Patent Document 9 is an example of using a vertical power tong and using a 9-5 / 8" short pin to perform a test evaluation at a 5-degree offset.
[0049] Non-patent document 2 is a paper evaluating lubrication by placing a 5 kN (about 500 kg) weight on the upper end of a short pin at the front end opposite to the tightening side of the short pin, that is, when the pin is tightened upright, using a vertical power tong.
[0050] Prior art literature
[0051] Patent Literature
[0052] Patent Document 1: Japanese Patent Application No. 2015-506445
[0053] Patent Document 2: Japanese Patent No. 5722752
[0054] Patent Document 3: Japanese Patent Application No. 2008-527249
[0055] Patent Document 4: Japanese Patent Application No. 2004-53013
[0056] Patent Document 5: Japanese Patent Application Publication No. 2016-028211
[0057] Patent Document 6: Japanese Patent Application Publication No. 2008-537062
[0058] Patent Document 7: Re-publication No. 2009-057754
[0059] Patent Document 8: Japanese Patent Application Publication No. 2002-327874
[0060] Patent Document 9: WO2017 / 110685
[0061] Non-patent literature
[0062] Non-patent literature 1: Steven S. Shademan; John W. Martin; Al P. Davis, NACECORROSION 2012, Paper No 2012-1095
[0063] Non-patent literature 2: Jinli et al.: Journal of Petroleum Technology Association, Vol. 61, No. 6 (1996) pp. 527-536. Summary of the invention
[0064] Problems to be solved by the invention
[0065] There have been few designs for coating agents that use a water-soluble or water-dispersible polymer as a binder resin as a matrix component and disperse metal soap and graphite as a solid lubricant in the polymer. Graphite is hereinafter also referred to as graphite.
[0066] The metal soap described in the present invention refers to the salt of metal ions other than alkali metals and higher fatty acids. Alkaline soap is the so-called soap used in daily life, which is defined as the salt of Na ions or K ions among alkali metal ions and higher fatty acids. Alkali metal salts other than Na and K are treated as metal soaps.
[0067] Here, in the present invention, the case of a reagent based on an aqueous solvent is also considered. An aqueous solvent refers to a solvent whose main component is water.
[0068] In this case, the metal soap itself is water-repellent and insoluble in water, so it is difficult to mix it into an aqueous solvent. It is said that the metal soap is also insoluble in the alcohol group. The metal soap slightly dissolves VOC (volatile organic compounds) and is a reagent group called a diluent. However, this reagent group is known as a reagent that is classified into the VOC group of toluene, xylene, benzene, mineral spirits, the ether group, and oils widely called mineral oils, which are mostly harmful to health.
[0069] Thus, it was previously considered difficult to directly mix the metal soap itself into the water-based polymer. Therefore, in the past, the metal soap was prepared by dissolving the metal soap itself in the VOC listed above and then making it turbid in a solvent mainly composed of water. Moreover, when the water volatilizes / evaporates, the VOC also flies away at the same time. Therefore, as a result, the metal soap can be dispersed in a water-soluble or water-dispersible polymer. This is exemplified in patent documents 5 to 7, for example. However, due to considerations for the safety of the operator and the environment, as well as considerations for the environment, and the volatilization of the reagent group called the diluent in places where fireworks are strictly prohibited, there is a high possibility that it cannot be used. Places where fireworks are strictly prohibited include, for example, oil / gas mining environments.
[0070] Aqueous (water-soluble or water-dispersible) polymers refer to polymers whose main component of the solvent is water. When the coating reagent is formed into a film, the water component needs to be dried and removed. Since the solvent of aqueous polymers is water, there is a method of heating the object to be coated during drying, or conversely heating the position of the object to be coated before coating. In either case, if there is no process to promote the volatilization / evaporation of water, a long waiting time is generated for drying, which becomes inefficient. However, in the case of well site repair, since it is a strictly prohibited area for fireworks, it is expected that it can be dried without using a heater, etc. and just by leaving it. Alternatively, it is also expected that a dry environment based on a blower based on compressed air is used more frequently in the supply to the well site, so drying can be considered. The drying environment is, for example, a condition of atmospheric temperature + (about 5°C to 10°C).
[0071] On the other hand, in order to dry the water-based polymer early, it is also known that a volatile organic solvent is added to effectively utilize the heat of volatilization to form a film. For example, Patent Document 5 states that in order to make the surface film of acrylic silicon become a dry film at a relatively low temperature and in a short time, an oily substance can be selected. Moreover, it is recorded that it is particularly preferred to use a room temperature curing substance. That is, Patent Document 5 is an example of achieving early drying by effectively utilizing the volatilization of an oily solvent without selecting a water-based system.
[0072] In addition, Patent Document 6 exemplifies a water-based system alone, a water+volatile organic solvent system, and a system using an ultraviolet curing resin. The latter two allow for early drying. However, for the first polymer of the water-based system alone, it is necessary to use some method to evaporate water. However, Patent Document 6 does not explicitly describe this method.
[0073] In addition, Patent Document 7 discloses a method of accelerating the drying time by using a volatile solvent and a reagent with a flash point of 30°C or more. However, when the flash point is about 30°C, in hot areas such as desert areas in midsummer, if there are dangerous factors such as sparks, the possibility of fire at the well site is also high. Moreover, even if processing is carried out in a workshop slightly away from the well, the concern about fire cannot be denied. If materials with low flash points, that is, materials that are easily ignited, are not used in a fully managed environment, there is a problem that the concern about accidents such as fires increases. That is, how to dry safely and early still remains a problem.
[0074] Based on the above, the inventors determined that since the well site is an environment where fireworks are strictly prohibited, the use of VOC (volatile organic compounds) and the reagent group called diluent (organic solvents such as toluene, xylene, benzene, etc.) in order to accelerate the drying of water-based solvents should be avoided. This is because, even if they are highly volatile and effective for early drying, there are regulations to suppress VOC emissions. In addition, they are insoluble in water, so they are not easy to use.
[0075] In addition, even if an exhaust device is prepared, it may become a huge equipment investment. Therefore, when forming a solid lubricating film, there is a problem that it is difficult to use a volatile organic solvent (VOC) that is harmful to the body as a coating agent. Therefore, the present inventors have determined that a reagent set called a diluent that is harmful to health and has too high volatility cannot be used to achieve early drying.
[0076] In addition, the use of fluorine-based solvents (such as Freon substitutes) that originally had quick-drying properties and fluorine-based resins that can be dissolved in them to form binder resin components of coatings has recently been changing towards being banned. Fluorine-based compounds have always been quick-drying and dry immediately from the tip of the coating, and have excellent lubricity and corrosion resistance, making them a typical surface treatment. However, due to the recent strengthening of regulations, fluorine-based compounds have become unusable. In the U.S. TSCA (Toxic Substances Control Act) and the European chemical reagent regulation REACH, F-based alkyl compounds (F-(CF2) n -) So far, only PFOS (perfluorooctane sulfonic acid) and PFOA (perfluorooctanoic acid) are regulated (chemical species containing fluorine compounds with 8 carbon atoms). There are no special problems with fluorine-based compounds with fewer carbon atoms than these compounds and they can be used. However, in the April 2021 revision of the US TSCA, the importation of PFAS (organic fluorine compounds: perfluoroalkyl compounds and polyfluoroalkyl compounds) reagents into the United States for use and production has almost become a complete NG. As a result, it has become a situation where binder resins containing fluorine compounds (PFAS) cannot be used. Therefore, the current situation has become that the only reagents / products that can be used in a fluorine-containing manner are Teflon (registered trademark) (PTFE: polytetrafluoroethylene), PFPE (perfluoropolyether), and HFE (hydrogen fluoroethylene), which are fluorine-based solvents of solvents. In addition, the international trend of designing solid lubricating films in the direction of not using fluorine can no longer be ignored.
[0077] Therefore, in order to deal with the environment, it is desired to use water as a solvent and a binder resin that is soluble in water. In addition, it is desired that such a reagent be used for repairing well sites and forming a top coating for improving lubrication by using appropriate solid lubricants and other additives.
[0078] In addition, there is a problem that when the solid lubricating film is formed using the reagent, water as a solvent is difficult to volatilize and takes time to evaporate.
[0079] For the purpose of repair at the well site and the reagents used for forming the top coating for improving lubrication, it is necessary to assume that they will be used at the well site. At the same time, the well site is an environment where fireworks are strictly prohibited, and there are also situations where the scaffolding is not firm. Therefore, it is also difficult to consider the installation of a device to enhance drying. In the case of applying a water-soluble or water-dispersible polymer-based reagent at the well site, rapid drying is required. The reason is that when a failure occurs in the well, the connection part that is the problem needs to be removed immediately for maintenance. In addition, this is because it needs to be repaired and tightened again afterwards. In addition, the reason is that the rental cost of the power clamp of the tightening device itself is huge, and even if it is small, it is necessary to lay as many as possible without stopping. The above-mentioned repair refers to the local repair of the burnt part at the well site.
[0080] Here, in Patent Documents 1 to 3, organic solvents with low or very low flash points and high volatility are used for early geomembrane formation. That is, the coating reagents are designed based on the premise of production and transportation at locations far from oil / gas wells. It is extremely dangerous to use reagents based on reagents with low flash points near oil / gas wells where fireworks are strictly prohibited.
[0081] Furthermore, the evaluation of lubrication characteristics based on the repair at the well site is not at a level that can be evaluated by simple laboratory experiments and simulations in the past. Therefore, the evaluation of lubrication characteristics based on the repair at the well site is preferably set to be able to cope with the most stringent conditions that can be imagined.
[0082] In actual wells, the threaded joint is subjected to strict conditions such as the deadweight of a pin of actual length, so it is not always possible to simulate this condition in the evaluation using a short pin in the laboratory. Therefore, unless the upper and lower limits of parameters such as the upper and lower limits of the composition of the solid lubricating film are set by designing conditions that reproduce actual wells or conditions close to those of wells, the regulations are meaningless. In other words, it is necessary to perform the evaluation under conditions close to actual wells on the basis of forming the burning conditions with high accuracy.
[0083] That is, in the case of evaluating the lubrication of oil well pipe threads using a solid lubricating film, if it is judged as NG in the previous tightening test in the laboratory using only a short pin of about 1m, it can also be judged as NG in the actual well. However, the inventors have obtained the following insight: there is no guarantee that a sample evaluated as OK in the laboratory using a short pin of about 1m will be OK in the actual well. However, in the past, there were very few cases where attention was paid to this fact and it was assumed that the lubricity of the solid lubricating film could be judged based on the conditions of the actual well. That is, in the existing literature in the past, when setting or explaining the specified range of the upper and lower limits of the parameters of the solid lubricating film, this point was rarely considered.
[0084] However, there is not much difference between the tightening and loosening evaluation of the viscous liquid lubricating compound commonly used in the lubrication of oil well pipe threads in the laboratory using a short pin and the actual situation in the well. The viscous liquid lubricating compound has a tendency to be linked to the evaluation in the actual well according to the evaluation in the laboratory. This is assumed to be effective because the lubricating compound is in the form of a viscous liquid, so it is effective to move the compound in a linked manner during tightening and loosening. In contrast, when a solid lubricating film is used, the fragments from the solid lubricating film that is inevitably ground during tightening and loosening do not necessarily move in a linked manner. Therefore, in the tightening of the actual well where the generation of fragments will increase anyway, the fragments are easy to clog. In addition, when peeling occurs significantly, burns occur in the part where the solid lubricating film becomes thinner and the part where the solid lubricating film disappears. In the evaluation of the solid lubricating film, it is necessary to make an evaluation based on this.
[0085] In actual wells, the actual length of the pin thread is not tightened to the sleeve thread in the ideal state as described in textbooks. The ideal state is the state where the actual length pin is inserted and set upright in the sleeve thread and tightened straight ( Figure 4 (b)). However, this is an impossible situation for a practical pin of actual length.
[0086] The structure of the oil well pipe thread is a tapered thread structure, and the pin thread enters the sleeve thread in the form of insertion. If it is a light and short short pin, it is easy to handle, and the short pin is mostly set straight ( Figure 4 (a)). At this time, there is "play (looseness, margin)" in the incomplete thread part of the tapered thread structure. In the case of a short pin, it can be tightened by hand to the vicinity of the shoulder ( Figure 2 , Figure 4 (b)). The incomplete thread portion refers to a portion where, for example, the thread is incomplete, the thread height, or the thread bottom is small.
[0087] On the other hand, the heavy and long actual length pin is hoisted by a crane for installation, but it is impossible to set it straight and ideally suspended directly below. In the initial installation, it is often installed slightly tilted by the amount of thread play ( Figure 5 ). In addition, it is impossible to tighten the screw by hand, and it is very common that the pin thread is exposed by about half of the total number of thread teeth relative to the sleeve thread. Figure 3 ). Oil well pipes are, for example, Figure 5Such a tapered thread structure. Therefore, before touching the shoulder, the meshing of the threads gradually converges to the original ideal position, but at this time, the pin thread swings with the amount of play. Therefore, before the threads mesh with each other, the thread surfaces of each other are sometimes damaged a lot. In addition, the deadweight (large load) of the pin thread is superimposed on the eccentric load used to move the pin offset, that is, the eccentric load when the pin swings. As a result, in the most stringent conditions, there is a high concern that the solid lubricating film is abnormally ground or stripped off without leaving any. If the fragments are blocked in the thread gap, it will directly cause burns. In the case where the fragments and powder of the ground solid lubricating film form secondary products, it is also easy to block the thread gap, thereby increasing the occurrence of burns. On the other hand, in the case of lubrication of oil well pipe threads using lubricating compounds, the lubricant is a viscous liquid. Therefore, since it can move in conjunction with tightening / loosening, the evaluation method of lubrication in the laboratory using a short pin is roughly the same as the results in the actual well, which is a good comparison. That is, it is a problem unique to the solid lubricating film.
[0088] Specifically show it in Figure 3 middle. Figure 3 The tightening and loosening test conditions are to rotate at 15 to 25 rpm before the torque rises and at 2.5 to 1.5 rpm after the torque rises. This is the result of testing under strict conditions, such as fast rotation speed, beyond the conditions specified in the thread operation manual (tightening instructions in the Technical package). The well fastening material and the strength grade 9-5 / 8” 53.5#Q125 raw material are made of JFELION TM The threads are designed to be lubricated by a solid lubricating film. Figure 2 This is a torque rotation diagram when using a short pin of about 1m and tightening with a vertical power tong. Since it is short, it is not difficult to operate and can be set straight. In addition, by manually tightening, the pin thread can be set with almost no exposure ( Figure 2 (b)). In the torque rotation diagram in this case, Figure 2 As shown in (a), the torque starts to rise from the time when tightening is started with the pliers, and tightening is performed by exceeding the bending point of the shoulder torque. This is a very common figure in test equipment in the laboratory, tightening in the factory with the axes of the pin thread and the sleeve thread aligned, that is, tightening using a horizontal power tong. The former condition refers to the following situation: since the pin thread is short and easy to handle, the pin thread can be set straight, and it can be set manually until the pin thread teeth are blocked by the sleeve thread. The latter condition refers to the following situation: when the long tube of the pin thread is placed horizontally, when the sleeve thread is installed, the shorter side is set, so there is no axial deviation, and the sleeve thread can be set straight. The torque rises immediately from the start of the pin rotation because the pin thread and the sleeve thread are fully engaged in the initial setting stage. Figure 2 The horizontal axis is about 1.5 turns. In addition, Figure 2 This is an example of a situation where the tightening start position using a power tong can be finally tightened by manual tightening.
[0089] on the other hand, Figure 3 This is a torque rotation diagram for a Range-3 pin, which is an actual length of more than 40 feet (more than 12 meters). Figure 3 is the result of the test in the simulated well. Figure 2 Different. It should be noted that the simulated well is not an actual well that produces oil / gas, but an experimental well with holes opened in a simulated manner so that actual length pins can be tightened and loosened. It has a stand that can hang about 2 to 3 connected pins from its ceiling. The simulated well refers to a device group or experimental facility that can perform tightening and loosening tests in such a structure. However, if Figure 3 As shown in (b), the initial setting position can only be set to a position where the thread is exposed about halfway in the case of the actual length pin. Figure 5 As shown, it is slightly tilted. However, this state is caused by a slight tilt with a level that cannot be visually recognized. Moreover, due to this state, the initial setting position of the thread is stopped halfway. Figure 3 (a) is the torque rotation diagram. This example shows the tendency of the same installation as in the actual well. However, it is different from the short pin. Figure 2 (a) is different. Figure 3 (a) has the characteristic of idling without increasing torque. Figure 3 In the example (a), the stable torque does not rise until about 6.3 revolutions, and a spike-like torque rise is observed from time to time during the rotation. The inventors have obtained the following insights: the spike-like torque is directly related to the damage of the solid lubricating film, and it is suggested that it is important to evaluate the solid lubricating film based on this. Figure 3 In the diagram (a), the situation where the torque does not increase and the vehicle idles is equivalent to the situation where the vehicle idles. Figure 5 Tightening from the state of being in engagement with each other to the point of just about touching the shoulder. In most cases, the threads are not fully engaged with each other, and a part of them accidentally touches strongly, resulting in a state of no further movement. Therefore, if a power tong is used for tightening, then for an actual length pin, the sleeve thread and the pin thread touch each other under a load offset state before the threads engage with each other. In other words, the sleeve thread and the pin thread damage each other. If the solid lubricating film is not evaluated on this basis, as mentioned above, a sample that is OK in the evaluation using a short pin may not necessarily be OK in the actual well. For this reason, it is believed that in the existing literature in the past, the upper and lower limits of parameters such as composition and conditions were mostly stipulated based on the laboratory evaluation of the short pin as mentioned above, and it is believed that it does not necessarily mean a good range.
[0090] Here, as documents that recognize the actual tightening of a well, there are, for example, Patent Documents 8 and 9, and Non-Patent Document 2. However, Patent Documents 8 and 9 are evaluations using short pins.
[0091] On the other hand, non-patent document 2 is a paper that uses a vertical power tong and places a 5kN weight on the upper end of a short pin to evaluate lubrication. In non-patent document 2, judging from the torque rotation diagram of a 7" 29# pin, it is believed that the weight of a pin of an actual length, that is, about 40 feet (about 12m), was intended to be applied. However, judging from the torque rotation diagram, this is not the case. Figure 3 (a) but close to Figure 2 (a) Tightening behavior. That is, the initial setting position is tightened by manual tightening to a level where the pin thread is not exposed, and the evaluation test after tightening is judged based on the state in which the pin thread and the sleeve thread are fully engaged. Therefore, in Non-Patent Document 2, it is impossible to simulate the situation that occurs in an actual well.
[0092] The present invention has been completed with a view to the above-mentioned problems, and its object is to provide a coating agent that does not use MoS2, is environmentally friendly, and can withstand use in actual wells as a coating agent for repairing and improving lubrication of the threaded portion of an oil well pipe.
[0093] Methods used to solve problems
[0094] The present invention is directed to a lubrication technology for oil well pipe threads using a solid lubricating film.
[0095] The present invention relates to an agent used for repairing at a well site when only the threaded portion of the threaded portion and the sealing portion of the oil well pipe thread components is slightly burned, for example, during lubrication of an oil well pipe threaded joint. The present invention relates to an agent, the purpose of which is to apply the agent to the area including the cured portion for the purpose of repairing after the burned portion is cured by grinding with a grinder, sandpaper, file, etc.
[0096] In addition, the present invention also aims to form a top coat using the agent of the present invention to improve lubricity when the lubricity of an already formed solid lubricating film needs to be further improved by one level. That is, it also includes coating on an already existing solid lubricating film to avoid burning, including preventive significance.
[0097] In order to achieve these objects, the present invention was completed by extracting problems from the above-mentioned prior art group and taking the following conditions into consideration.
[0098] As a reagent, composition design was performed without using MoS2 with concerns about cracking.
[0099] From an ecological point of view, the reagent is designed based on water-soluble substances in order to ensure the safety of workers and to be used even under conditions where fireworks are strictly prohibited. At the same time, the water in the solvent is dried up early in order to form a membrane.
[0100] Solid lubricants do not contain harmful heavy metals such as Pb.
[0101] Furthermore, as constituent elements of the binder resin, no PFAS (fluorinated acrylic acid groups including PFOS and PFOA)-containing agents or alternative fluorine-based solvents with high global warming potentials are used.
[0102] The present invention is designed to add graphite and metal soap as solid lubricants to water-based polymers. Graphite and metal soap are insoluble in water, but slightly soluble in alcohol. In the present invention, the graphite and metal soap are dissolved by conducting research on dissolving the graphite and metal soap in alcohol in advance and then mixing them into the stock solution of the water-based polymer. Otherwise, the graphite and metal soap cannot be uniformly dispersed in the solvent mainly composed of water. In addition, while uniformly dispersing, the necessary content for lubrication and early drying is clarified.
[0103] In addition, the inventors have obtained the following insights: when graphite is used as a solid lubricant, when tightening and loosening, the graphite as a solid lubricant is integrated with the binder resin, and sometimes stretches long to form a ribbon-shaped secondary product. Moreover, the inventors have obtained the following insights: the ribbon-shaped secondary product becomes a cause of the risk of burns. Therefore, it is suggested that even if lubrication assistance is achieved by combining a solid lubricant of a metal soap with the binder resin of the present invention, in the case of lubrication using graphite, there is an appropriate amount of addition in order to prevent the ribbon-shaped secondary product from causing burns.
[0104] Here, the present invention is designed to use a water-soluble or water-dispersible polymer so that the solid lubricant is dispersed relative to the binder resin of the soft polymer resin film when the film is dried. In addition, one of the characteristics is that metal soap and graphite are mixed as solid lubricants.
[0105] In the present invention, the graphite has a portion held together with the polymer and a portion not completely held by the polymer but exposed as a graphite monomer and responsible for lubrication. In short, the graphite plays a role in maintaining lubricity in combination with the lubrication of the metal soap.
[0106] Graphite is widely used as a lubricant. However, in the case of a structure with grooves such as oil well pipe threads and a dry film such as a solid lubricating film, the "escape path (direction of extension and deformation)" of the lubricating component graphite when it is pressed and deformed is limited. Therefore, when the threaded joint is tightened with a strong force, black strip-shaped flakes are easily formed along the thread groove. Moreover, this easily blocks the gap between the threads and causes burns. According to the observations of the inventors, for example, for a film composed of graphite (solid lubricant) and epoxy resin (adhesive resin), when the proportion of graphite is high, the following insights are obtained. That is, examples can be seen everywhere where a group of strip-shaped fragments composed of graphite and adhesive resin are blocked in the gap of the thread when tightening and loosening, causing burns.
[0107] In addition, this phenomenon has not been reported in other lubrication fields. When graphite is dispersed in a solvent or oil and used as a lubricant, it is not likely to be a problem. In addition, in lubrication in other fields, no strip-shaped flakes are formed, and graphite tends to become powdery and fine flakes. Therefore, graphite is easy to move in conjunction with tightening and loosening, so it is not easy to cause burn problems. If it is not in a state of being retained by an organic resin such as an adhesive resin, part of the graphite is transferred to the surfaces of two objects that are in a sliding state. In this case, it becomes a polished state, which improves lubrication. Polishing refers to a luster with a metallic luster. In addition, when MoS2 is dissolved in a mineral oil system to a synthetic oil system such as Molykote, there is almost no problem with the graphite in the dissolved state at the same time.
[0108] In contrast, the present invention uses a water-soluble or water-dispersible polymer and uses it as a film after water is scattered. Therefore, the focus is mainly on dry environments. As a result, the polymer raw materials of the binder resin and graphite constituting the solid lubricating film may become black bands under the constraints of the thread groove, which may cause burns. In this way, the following understanding is obtained: in the formation of the solid lubricating film, in order to use the graphite of the solid lubricant, it is necessary to design the amount, size, etc.
[0109] Therefore, in the present invention, graphite is used as a solid lubricant, but during tightening and loosening, a component design is performed to suppress the graphite as a solid lubricant from integrating with the binder resin and stretching long to form a ribbon-shaped secondary product. This can reduce the risk of burning.
[0110] In addition, in the partial repair or the coating of the entire surface by repair, the composition design different from the previous concept is carried out. That is, the composition design is designed to not only improve the lubricity but also to fill the repaired part that has been ground.
[0111] The solid lubricating film and reagent of the present invention are evaluated by an evaluation method that conforms to the environment used in actual wells, and the upper and lower limits of the parameters are set. Thus, a reagent and solid lubricating film that can assist lubrication or repair slightly burned parts and withstand use in actual wells are provided.
[0112] Next, the response to each condition will be described.
[0113] (1) Among those involved in oil / gas mining, there is a deep-rooted idea that MoS2 will eventually turn into H2S, or has a high probability of causing hydrogen embrittlement cracks, regardless of the mechanism. In order to avoid the recognized risk factors reported in non-patent document 1, it is necessary to deal with a component system that does not use MoS2. Moreover, in the present invention, the following sprays, pastes, liquid lubricating sprays, and lubricating coatings are not used. That is, MoS2 is contained as the main component as the widely popular Molykote and its similar products. Moreover, solid lubricants such as PTFE, graphite, BN, and silicon are added according to the situation. Furthermore, sprays that expand mineral oil-synthetic oil systems (white mineral oil, PAO, PAG, etc.) in solvents are not used in the present invention.
[0114] At the same time, in order to achieve well site repair (local repair of solid lubricating film) and further improve the lubrication performance of oil well pipe threads, alternative materials are used for component design to achieve equivalent to or better performance.
[0115] (2) In the present invention, in order to cope with ecology and utilization at well sites, the reagent design is based on a water-soluble substance. Based on this premise, the water of the applied reagent is volatilized / evaporated early to form a film.
[0116] Even in places where fireworks are strictly prohibited, such as well sites, coating is required. However, in order to achieve early drying, VOC (volatile organic solvents) such as toluene, xylene, benzene, etc., which are volatile organic solvents of specific chemical substances, cannot be used for water solvents. Therefore, some methods are needed to achieve early drying. Regarding specific chemical substances, for example, if it is the United States, it corresponds to OSHA, and if it is the rules of the U.S. Occupational Safety and Health Administration, it corresponds to the working environment measurement target substances.
[0117] In addition, for early drying (quick drying), it is also conceivable to use highly volatile but non-flammable fluorine-based solvents and fluorine-based adhesive resins, but this is actually impossible. In the U.S. TSCA (Toxic Substances Control Act), after the revision of the rules at the end of April 2021, even with past permission, a set of reagents containing PFAS (fluorinated alkyl groups including PFOS and PFOA) cannot be used retroactively. Moreover, with the recent increase in environmental awareness, various countries may also follow the above rules. For the reagent rules that are becoming stricter year by year, it can also be said that HFE, which replaces Freon, is still possible to use, but it is best to design in the direction of not using it.
[0118] Therefore, in the present invention, it is not possible to achieve quick drying like drying after coating by methods other than fluorine-based and diluent-based VOC (volatile organic compounds). However, as a goal that can be achieved by using water-based methods, it has an early drying performance of the degree that it can be dried within 30 minutes, preferably within 15 minutes, and more preferably within 5 minutes in an environment around room temperature.
[0119] In the vicinity of oil / gas excavation sites, in an environment where fireworks are strictly prohibited, in addition to using hot air heaters that can promote drying, it is also strictly prohibited to use devices that generate electric sparks. For heat treatment furnaces, it is also necessary to assume an environment where no electricity is used and they are only placed in the atmosphere. Therefore, it is impossible to imagine a process in which the solvent is dispersed by heat treatment at about 50°C to about 300°C. Patent documents 5 to 7 describe the use of highly volatile organic solvents to achieve early drying. However, it cannot be used in the environment envisioned by the present invention. In addition, ultraviolet curing resins such as patent document 5 also mean that a device capable of irradiating ultraviolet rays is required at the well site. Therefore, it is necessary to distribute electricity with a device that can perform this operation, and as a method for early drying, it has to be said that there is a lack of feasibility. If it is a factory or workshop that manufactures products with solid lubricating films, it is not an environment where fireworks are strictly prohibited like a well site, so it is easy to prepare air supply equipment such as large fans, hot air drying equipment, heat treatment, infrared light, ultraviolet light and other drying enhancement equipment. However, as the most stringent use condition, it is necessary to assume that only drying enhancement such as compressed air is performed, and it is difficult to use an electric heater when fireworks are strictly prohibited.
[0120] When drying is performed using such a device for accelerating drying, the present invention preferably performs drying within 5 minutes, preferably within 3 minutes, and more preferably within 1 minute. As for the use conditions at the well site and the use conditions in the production line, it can be dealt with without slowing down the production line speed. Therefore, in order to dry within the production cycle time of the production line, early drying is also a goal.
[0121] (3) At the same time, in order to cope with the recent increase in environmental awareness, harmful heavy metals represented by Pb are not used in solid lubricants. In addition, as a constituent element of the binder resin, a set of reagents containing PFAS (fluorinated acrylic groups including PFOS and PFOA) are not used. Under this condition, in the present invention, properties comparable to those of lubricating sprays, pastes, and coatings containing MoS2 are achieved. The former is designed in a way to avoid addition. The latter is as described in (2) above.
[0122] (4) The present invention is designed to contain graphite and metal soap in a water-based polymer, particularly a water-based acrylic film or a water-based methacrylic film.
[0123] In particular, metal soaps are insoluble in water and alcohol. Therefore, research is required to mix the metal soap with the stock solution of the aqueous polymer in a nearly homogeneous state.
[0124] Similarly, when graphite is used as a lubricant by itself, a material obtained by mixing and dispersing graphite with an appropriate amount of additives in a solvent such as an aqueous solubility solvent or oil is used. Therefore, in order to uniformly disperse the graphite in a solvent mainly composed of water, a research is required to dissolve the graphite in an aqueous solvent, similar to metal soaps.
[0125] Metal soap and graphite are easily dissolved in a reagent group called a diluent such as oil, ether, or VOC (volatile organic compound). However, the present invention does not use a reagent group called a diluent, and it is necessary to study how to dissolve metal soap and graphite in a solvent composed of water.
[0126] Patent Documents 5 to 7 are examples of promoting the volatilization of aqueous solvents by mixing with VOCs of the diluent system and effectively utilizing their volatility. However, in the present invention, the goal is to be able to use it in the strictly prohibited pyrotechnic environment of the well site under the most stringent use conditions, so the use of organic solvents of the diluent system based on these conceived methods is not envisioned.
[0127] (5) At the same time, when the graphite is tightened and relaxed, the graphite and the binder resin are integrated, and in order to prevent the graphite from stretching out and forming a ribbon-like secondary product, it is necessary to study the component design and mixing ratio.
[0128] In addition, during repair, after curing with a grinder or sandpaper, the reagent of the present invention is applied. At this time, sometimes the solid lubricating film disappears, or a part is missing, or the metal of the threaded part is also ground and disappears. The following research is conducted: by graphite, the ground repaired part is buried, lubrication is achieved, and a secondary product that does not stretch long to form a strip is achieved. That is, so as not to form a material that is as long as about 30 mm. In addition, even if it is a strip, it is short and fragmentary, and if possible, the graphite is scattered in a powdery state. That is, the solid lubricant composed of graphite is evenly transferred to the sleeve thread and the pin thread. That is, no secondary products in the form of strips are formed, and the powdery or small fragmentary secondary products from the solid lubricating film or these secondary products move in conjunction with tightening and loosening, and do not block the thread gap. Even when graphite is selected as a solid lubricant, this state can be stably achieved.
[0129] In addition, the present invention is different from the technical concept of forming a two-layer structure in the unused stage as in Patent Documents 1 to 4. The present invention is not necessarily consistent with a two-layer structure in which the outermost layer is partially reinforced by a hard film, or a high-strength film is used as the uppermost layer to protect the viscoelastic film below. These methods cannot be methods for solving the problems intended by the present invention. In the present invention, sometimes a part also becomes a two-layer structure, but the application field is different.
[0130] In addition, the concept of the prior art, which has no binder resin and only a lubricant on the outermost layer, is also different from the present invention. The present invention includes a solid lubricant that enters the film in the presence of a soft binder resin. At the same time, it also includes a situation where other types of solid lubricating films exist in addition to the binder resin. This is different from the technical concept of the conventional lubricating spray.
[0131] (6) The solid lubricating film and coating agent of the present invention are evaluated by an evaluation method that conforms to the environment used in actual wells. In addition, it is necessary to set upper and lower limits of parameters to complete lubrication assistance or coating agents that can repair slightly burned parts. In the evaluation using a short pin of about 1m, the evaluation method is not in accordance with the actual conditions of use. Therefore, new research has been conducted on the evaluation method. That is, a new appropriate evaluation method has been proposed. That is, the strict conditions in the actual well where the dead weight of the actual length pin is applied to the sleeve thread, and the threads are tightened in an offset state, are reproduced, and the evaluation is performed including the influence of the offset load caused by the application of the dead weight, thereby providing the accuracy of the parameters of the present invention.
[0132] Here, the methods shown in Patent Documents 8 and 9 are the results of setting the offset at 5 or 6 degrees and conducting a tightening test with a short pin. However, this is considered to be an example that has not become a harsh test in reality. The pass / fail judgment evaluated by these methods may not always be carried out smoothly. In fact, when the offset is set to 5 or 6 degrees and a short pin is used to conduct a tightening and loosening test, the following situation is assumed. That is, the inclination of the pin thread is determined by the margin of fit between the incomplete threaded portion of the sleeve thread and the tapered portion at the front end of the pin thread. Therefore, even if it is set at 5 or 6 degrees and inserted, it is difficult in terms of the structure of the thread. As Figure 4 (a) Figure 4 As shown in (b), the thread has a taper. The initial looseness is caused only by a slight difference in the meshing of the threads, and 5 to 6 degrees is not realistically possible. The top of the external thread (pin) and the top of the internal thread (coupling) abut each other halfway. Therefore, the taper angle of the thread teeth cannot be absolutely tilted in structure. At the same time, even if it is completed in an instant, it cannot be maintained for several turns. If several turns are tightened manually, the pin thread stands up and is set straight. Therefore, only the initial moment of the pin thread tip and the middle of the sleeve thread are violent, which will not be a particularly harsh condition.
[0133] Figure 5 This is a typical example of a situation where a real-length pin, i.e., a pin of about 40 feet (≈ about 12 meters), is set. The pin is long and heavy. Therefore, even if it is lifted by a hydraulic crane using a compensator and a lifting guide, the real-length pin cannot be set vertically. The pin is set slightly bent, and after only a few turns by manual tightening, it gets stuck in the middle and stops moving forward. In actual wells, Figure 5 Status to Figure 4 (b) The unreasonable rotation of the state. If it is not evaluated based on simulation, it is impossible to accurately define the upper and lower limits of the parameters.
[0134] This is the same as the existing literature in the past. In order to make the prescribed range meaningful, it is necessary to evaluate lubricity by tightening and loosening in an actual well, a simulated well, or a new evaluation method that can perform simulations consistent with these.
[0135] The present invention is a coating agent in which a water-soluble or water-dispersible polymer (aqueous polymer) is used as a binder resin, a mixture of a metal soap and graphite is used as a solid lubricant, and a solvent is a system containing water as a main component.
[0136] In addition, the present invention is a repair technology for the case where, for example, slight burns occur only in the threaded tooth portion of the constituent element (threaded portion) of the oil well pipe thread and the threaded tooth portion in the sealing portion during lubrication of the oil well pipe threaded joint. That is, the present invention is a repair technology for repairing the well site. The burned portion is ground and maintained using a grinder, sandpaper, file, etc. Then, for the purpose of repairing the area including the oxidized portion, the repair is performed by applying the reagent of the present invention. Furthermore, the present invention relates to an oil well pipe threaded joint in a state where the reagent has been film-formed.
[0137] In the present invention, the water-soluble or water-dispersible polymer (aqueous polymer) is composed of a binder resin, the solid lubricant is composed of graphite and metal soap, and the solvent is mainly composed of water. The above-mentioned binder resin is mainly an aqueous acrylic resin and a methacrylic resin. In the following description, both aqueous acrylic resins and methacrylic resins are referred to as aqueous acrylic resins.
[0138] In addition, the present invention aims to improve lubricity when the lubricity of the solid lubricating film needs to be further improved. Alternatively, the present invention aims to avoid burning, including preventive significance. For such a purpose, the present invention also includes a technique for forming a top coating by coating on an already existing solid lubricating film.
[0139] In order to achieve this, the present invention is based on the premise that the metal soap is uniformly mixed in the coating agent. That is, it is based on the premise that the water-repellent and water-insoluble metal soap is uniformly blended.
[0140] In addition, when graphite is used as a solid lubricant, the amount of the water-based acrylic acid in the binder resin is balanced. Thus, the thread of the oil well pipe is used to make it into a fine powder or fragmented form so as not to form a band-shaped secondary product. In addition, the binder resin and graphite are appropriately balanced.
[0141] In addition, although early drying is required depending on the application, the reagent is prepared so that it can be used even in an environment where pyrotechnics are strictly prohibited at a well site.
[0142] By considering the above conditions in a manner that satisfies them, good restorative lubrication during local repair and improved lubricity of the solid lubricating film can be achieved within the range specified in the present invention. The present invention is constructed using the following novel solutions to solve the above problems.
[0143] Further details are given.
[0144] The reagent is designed not to contain MoS2, and the film after drying is designed not to contain MoS2.
[0145] In addition, mineral oil-synthetic oil white mineral oil, PAO (poly-α-olefin), PAG (polyalkylene glycol) and the like used in these commercially available lubricants are not used as solvents. In the present invention, graphite and metal soaps, which are completely different in technical system, are used as lubricants instead of MoS2.
[0146] The present invention is designed to use graphite and metal soap together as solid lubricants, and to disperse these solid lubricants in a water-based polymer using water as a solvent. In addition, it is designed to be able to dry early during film formation. In addition, by adding a small amount of alkaline soap, the lubricity is further improved.
[0147] In the past, metal soaps were mostly added to oils as additives to increase viscosity. In the present invention, metal soaps are not used as thickeners or thickeners. In the present invention, metal soaps are not added to increase the viscosity of oil-based solvents. In the present invention, metal soaps have the function of lubricants and as a means for early drying. Moreover, one of the characteristics of the present invention is that a water-repellent metal soap is dispersed in a water-based solvent for use.
[0148] Regarding this condition, in the basic configuration of the present invention, water is used as the main solvent, but on this basis, a lower alcohol having a carbon number of 3 or less is added to the water used as the solvent. The mixing ratio is set to be 0.5 or more and 10 or less relative to the volume of 100 of water, and the total volume of water and these additives constitutes 95% or more of the total solvent volume in terms of volume % (volume / volume %).
[0149] Furthermore, as an additive to the constituent components of the further solvent, ammonia water may be added. The present invention defines 28-30% ammonia water as so-called concentrated ammonia water. However, when using dilute ammonia water, the reading is replaced with a value converted by dividing according to the concentration.
[0150] The solid lubricant is set to a composition in which 95% or more of the weight of the total solid lubricant components are composed of graphite and metal soap. A solid lubricant is used in which graphite is blended in a range of 0.5% or more and 5% or less in the total solid lubricant components. In addition, alkaline soap may not be said to be a solid lubricant, but it works effectively for lubrication in a broad sense. The alkaline soap is designed to contain 1% or less, including zero.
[0151] The binder resin is a water-soluble or water-dispersible polymer. The composition of the coating agent is as follows: the binder resin is a polymer or copolymer containing 90% or more of a monomer belonging to an acrylate or methacrylate when the weight of the total binder resin is used as the denominator.
[0152] In addition, the present invention is not a composition in which a solid lubricant is added to an oil-based solvent like a large number of commercially available lubricating sprays and pastes. The present invention is a composition in which a binder resin component and a solid lubricant component are added to an aqueous solvent. Furthermore, it is designed that the substance formed into a film by volatilization / evaporation of water in the reagent functions as a solid lubricating film.
[0153] The reason for using a solvent mainly composed of water is to ensure the safety of workers, to enable use even under conditions where pyrotechnics are strictly prohibited, and to contain no harmful components.
[0154] In the present invention, graphite and metal soap are used as solid lubricants instead of MoS2. Graphite and metal soap are used together as lubricants. Both graphite and metal soap function to achieve good lubrication. Their combination brings good results. Figure 4 Lubrication from the state where the threads are meshed with each other as shown in (b) is also effective. In addition, when tightening the actual length pin thread, the pin is set slightly tilted (see Figure 5 ) until the pin thread is stably in a stable position (equivalent to Figure 3 Step 1) of (a) also functions effectively.
[0155] At the same time, lubrication is improved by also mixing an alkaline soap component. In the present invention, including no addition, the maximum is formulated to 1%. The alkaline soap component is the so-called "soap", which dissolves in water and increases the viscosity of the solvent. Furthermore, the alkaline soap component refers to a solid component including the part that enters the film or adheres to the surface of the solid lubricating film when drying. The alkaline soap component has the following two effects. That is, it has the following effects: the improvement of lubricity brought by the dry alkaline soap itself, on the other hand, the alkaline soap in the wet state dissolves and forms mucus, so that the lubricity functions in a good direction. Moreover, in actual wells, when the thread teeth are wetted by the reverse flow of mud, rainfall, frost, etc. that sometimes occurs, a soapy mucus attached to the surface or partially exposed is formed on the surface of the film. Moreover, it can also be expected that the alkaline soap component will play a function of accelerating lubrication. The reason for setting the upper limit below 1% is that the addition exceeding this value will excessively increase the viscosity of the reagent, making it difficult to apply evenly.
[0156] Since water is a solvent, a water-soluble or water-dispersible polymer is used as the binder resin. In this case, the polymer is a polymer or copolymer containing 90% or more of a monomer belonging to acrylate or methacrylate relative to the weight of the entire binder resin.
[0157] In addition, the following contents are described above. This description means that "the total volume of water and lower alcohols in the total solvent is 95% or more", or "the total volume of graphite and metal soap in the solid lubricant is 95% or more", or "the volume of acrylate and methacrylate in the binder resin is 90% or more". These descriptions mean that even if impurities, trace additives, or substances added unintentionally are mixed, as long as the level described here is allowed, it will not affect the characteristics.
[0158] In order to eliminate the difficulty of drying the reagent and ensure early drying, the present invention effectively utilizes the volatility of lower alcohols and possible volatility of ammonia, thereby increasing the volatilization / evaporation of water.
[0159] In addition, as a preferred range for promoting early drying, the size of the solid lubricant is set to an average particle size of both the metal soap and graphite of 5 μm or less. Furthermore, in the present invention, the addition amounts of the metal soap and graphite are optimized to achieve early drying.
[0160] The idea of reducing the particle size of the solid lubricant is to add a substance that increases the surface area in order to promote early drying of the coating agent that has not yet dried. Furthermore, this is because a solid lubricant of a microscopic size is effective for lubrication. From the viewpoint of both early drying and lubrication, the particle size of the solid lubricant is preferably 5 μm or less, and the smaller the better. The particle size of both the metal soap and graphite is preferably 1 μm or less.
[0161] In addition, in order to prevent the metal soap and graphite from forming a mass, it is necessary to mix them in a water-based solvent. The reason is that even if the initial particle size is small, when they are combined to form a block or a mass, the idea of increasing the surface area and accelerating drying cannot be realized. In addition, they are water-repellent and tend to be insoluble in water. Therefore, in order to dissolve them in a water-based solvent, they are temporarily dissolved in a lower alcohol used for early drying and then dissolved. As a result, they can be uniformly dispersed in an aqueous solvent.
[0162] In order to achieve both early drying and lubricity, it is important to make the blending ratio appropriate. In the present invention, the weight of the water-soluble or water-dispersible polymer, solid lubricant, and water-based solvent equivalent to the weight of all constituent components is set to 30% or more, 10% or more, and 40% or more as the lower limit, respectively. In addition, as the upper limit of each, it is preferably 40% or less, 20% or less, and 50% or less.
[0163] The reasons for setting this preferred range are as follows. It is possible to allow a situation where the reagent is dilute, i.e., a situation where there are many solvents, but the viscosity decreases, the viscosity becomes lower, and the fluidity of the reagent becomes higher. At the same time, because the water component becomes more, it takes drying time. Since the reagent is dilute, if it is repeatedly applied and dried each time, it is possible to make the reagent to ensure lubrication and rust-proof properties. However, the use convenience is poor and it is difficult to say that it is realistic.
[0164] In addition, under the premise of being dissolved in a solvent, it is important to prepare the weight ratio of the binder resin to the solid lubricant so that the weight ratio of the solid lubricant is between 0.25 and 0.66 relative to the weight of the binder resin. A weight ratio range of 0.3 or more and 0.5 is more preferred. The material result of this ratio is that a solid lubricating film is formed on the thread surface. In order to uniformly disperse the solid lubricant in the binder resin, there is a limit in terms of lubrication improvement. If there is too much solid lubricant, it cannot completely enter the film and only adheres to the surface, which is not conducive to maintaining lubrication improvement. Therefore, as a preferred range, the upper limit is 0.5. On the contrary, if it is too little, the solid lubricant required for lubrication will be too little, and the target level of lubrication cannot be maintained. Therefore, the preferred lower limit is 0.3.
[0165] In order to dry early and take measures to increase the volatility in the solvent, a lower alcohol with a carbon number of 3 or less is further added as an additive. Furthermore, ammonia water is added according to the situation. The total volume of these additives is 0.5 or more and 10 or less relative to the volume of water 100. The lower alcohol of the former is preferably adjusted to add 0.5 or more and 5 or less relative to the volume of water 100. Ammonia water is allowed to be mixed in a range of 0 or more and 5 or less relative to the volume of water 100. Ammonia water is sometimes intended to be used for pH adjustment. However, the volatility of ammonia is effectively utilized, and the reagent is also intended to be dried. Regarding ammonia water, it should be noted that the ammonia water described here is 28-30% ammonia water, i.e., so-called concentrated ammonia water. In the case of using dilute ammonia water, the reading is replaced with a numerical value converted by division according to the concentration.
[0166] Furthermore, in order to promote early drying, the mixing ratio of metal soap with a particle size of 5 μm or less and graphite is set to a weight ratio of graphite to the weight of the entire solid lubricant of 0.5% or more and 5% or less. Other solid lubricant additives of less than 5% are also allowed, but they are mixed so that the remaining main components other than the metal soap are mainly graphite.
[0167] Metal soaps function effectively for lubrication. However, if metal soaps are used in an environment where fireworks are strictly prohibited, there is a limit to using alcohol to dissolve the metal soaps in advance. In order to homogeneously mix the metal soaps in the coating agent composed of the aqueous polymer, the amount of metal soaps added is limited. Therefore, the upper limit is determined to be 5%. In addition, the lower limit of 0.5% or more is determined by the necessary amount to achieve early drying through the synergistic effect with fine graphite, and is stipulated in order to also achieve lubrication properties.
[0168] Meanwhile, in order to effectively utilize graphite as a lubricant using only graphite itself, a material prepared by mixing and dispersing graphite with appropriate additives in a water-based solubility solvent, oil, etc., has been used. In principle, graphite is insoluble in water, so reagent design is performed to homogeneously disperse graphite in a solvent mainly composed of water. As shown below, research is required to uniformly disperse graphite in the same manner as metal soaps.
[0169] In the coating agent, it is premised that the metal soap and graphite are uniformly mixed.
[0170] However, it is said that although metal soap is soluble in oil, it is water-repellent and insoluble in water. Therefore, metal soap is usually not well turbid in the water-based solvent of the present invention. Therefore, it is necessary to find a way. Similarly, graphite is also insoluble in water in principle. In the past, when only itself was effectively used as a lubricant, a substance obtained by adding additives to a solvent such as oil or a soluble solvent and mixing and dispersing the mixture was used. If no solution is found and graphite is directly dissolved in an aqueous solvent, there is a tendency to feel that the graphite floats on the surface. From the perspective of effectively using graphite as a solid lubricant, it is preferred to disperse the graphite as much as possible.
[0171] The solution is described.
[0172] Regarding metal soap, the present inventors obtained the following findings during laboratory research experiments in which a water-insoluble metal soap was mixed with a solvent auxiliary component added to water as a solvent for a water-soluble or water-dispersible polymer (aqueous polymer).
[0173] That is, metal soap is neither soluble in water nor in ethanol. However, when actually trying to dissolve it, when comparing water and a lower alcohol group represented by ethanol, it was observed that the dispersion and dissolution behavior of metal soap was different. In the lower alcohol group represented by ethanol, metal soap is not easy to form a mass, and has a tendency to be easily micronized, and the metal soap can be kept in a state of microparticles. The metal soap can be mixed with alcohol and then stirred strongly or vibrated using ultrasound. On the other hand, only by water, the metal soap will gather and become larger, forming a mass, and cannot be in a homogeneous dispersed state.
[0174] Therefore, the metal soap is temporarily dissolved in a lower alcohol group such as ethanol to make the metal soap insoluble but dispersed. Then, the present inventors conceived a coating material in which the metal soap can be dispersed nearly homogeneously by developing and mixing the metal soap in a water-based polymer.
[0175] Here, after the coating agent is left to stand, the metal soap separates over time. However, when the container containing the agent is vibrated to make it turbid again before coating, it can be confirmed that a homogeneous solid lubricating film is formed by scattering, i.e. evaporating / volatizing, the solvent water.
[0176] Note that, when the metal soap is directly dissolved in water, there is a tendency for the metal soap to form agglomerates, so when forming a solid lubricating film, there is a high possibility that an uneven film will be formed.
[0177] In the present invention, the metal soap is prepared by dispersing the metal soap in a lower alcohol to make it turbid and then adding the dispersed metal soap into water as a solvent. Thus, the metal soap can be prepared homogeneously.
[0178] As for graphite, lower alcohol can be effectively utilized in the same manner as the dissolution of metal soap into aqueous solvent. However, in the case where the ratio of lower alcohol to water is 10 or less as in the present invention, it is difficult to dissolve like metal soap. In this case, a part of the graphite floats on the surface of the solvent, but it can be dispersed by making most of the graphite dispersed, or by shaking the entire reagent before coating, etc. to make it uniformly dispersed.
[0179] From the viewpoint of improving the lubricating behavior described later, it is preferred to contain alkaline soap. Alkaline soap is soluble in water, so from the viewpoint of being soluble in a water-based solvent, there is no particular problem. In the present invention, it can be dissolved with 1% as the upper limit. Dissolution above 1% will increase the viscosity of the reagent as a whole, making it difficult to carry out homogeneous coating, and is therefore not good.
[0180] On the other hand, the present invention is intended to be a composition that can be used even in the most stringent environment where fireworks are strictly prohibited. Therefore, in the present invention, the three aspects of early drying, the technique of dissolving the metal soap in advance and then dissolving it in the aqueous solvent, and the flash point being adjusted to a high level to take safety into consideration are simultaneously achieved by using a lower alcohol.
[0181] Here, the target flash point is most preferably evaluated as a non-flammable state. However, it is considered that if the flash point of the reagent is an environment of 60°C or more, it can be used as long as it is an environment in which fireworks are strictly prohibited in the well site environment. Therefore, it is allowed to use lower alcohols to this level. It should be noted that the volatilization of ammonia can also be used. The flash point of ammonia water is non-flammable. In addition, ammonia water is also used to adjust the pH of acrylic adhesive resins that constitute coating reagents. Therefore, it is preferred to use ammonia water in a manner that is close to the upper limit of the pH adjustment range to increase the pH and utilize its volatility.
[0182] In addition, in the present invention, the main components of lubrication are metal soap and graphite. The graphite added to improve lubrication is designed so that it will not be integrated with the adhesive resin and stretched long to form a ribbon-shaped secondary product when tightening and loosening. In addition, by containing a small amount of alkaline soap, further lubrication improvement can be added.
[0183] Not only graphite, but also graphite is constrained along the thread groove in the state of a film of graphite and adhesive resin components. At the same time, the integration of graphite and adhesive resin also has an impact, and it is easy to form a secondary product in the form of a belt (like a box belt). They are difficult to move in conjunction with the tightening and loosening of the thread. As a result, it is easy to clog the thread gap, and as a result, the possibility of becoming a cause of burns becomes higher. Therefore, it is necessary to design the components in a way that the graphite is in powder form, fragment form, and not in a belt form.
[0184] Therefore, in the solid lubricating film composed of metal soap + graphite (and then a small amount of alkaline soap) and a binder resin, the goal is as follows. For example, the goal is to not form a band-shaped secondary product along the above-mentioned thread groove that causes burns when tightening and loosening, and even if a secondary product is formed, it is a peeling sheet or powdery secondary product that is separated from each other and does not cause burns. On the other hand, alkaline soap is easily dissolved in an aqueous solvent, so even if you don't realize it, you will feel that it is uniformly dispersed in the solvent. Therefore, when applying and drying, it becomes a style that is almost distributed in the film and a part is attached to the outermost surface.
[0185] As a method for achieving the above-mentioned style, in the present invention, a metal soap component is used as a main component relative to a binder resin, and the amount of graphite as a secondary component is limited. Graphite is effective for improving lubrication performance. However, when the sliding area of graphite is limited such as a thread structure and the path for the movement of solid lubricants and secondary products is limited to a narrower path, a secondary product in the form of a belt (like a cassette) is formed. As a result, it blocks the gap between the threads and has a higher tendency to induce burns. Therefore, graphite is formulated with a lower limit of 0.5% or more and an upper limit of 5% or less of the total weight of all solid lubricant components containing alkaline soap components.
[0186] Specifically, the lower limit is determined by the necessary content of graphite to achieve the lubrication improvement effect. In addition, the upper limit of the graphite content is determined by the fact that excessive addition of graphite will prevent the formation of band-shaped secondary products of the graphite main body when tightening and loosening the thread.
[0187] The structure of the solid lubricating film includes the following: starting from the state where graphite + metal soap completely enters the film, the graphite monomer is distributed to the extent that it is felt to be attached to the outermost surface of the solid lubricating film. In addition, the total amount of graphite relative to the total solid lubricant (including the alkaline soap content) needs to be less than the upper limit of 5%.
[0188] A more preferred range is preferably 1% or more and 3% or less. When the lower limit is set to 1% or more and the upper limit is set to 3% or less, the lubrication improvement effect brought by graphite can be further expected, and the formation of secondary products with a band structure can be more easily avoided.
[0189] In the present invention, metal soap and graphite and a small amount of alkaline soap are used to promote lubrication. The addition of graphite improves the insufficient lubrication behavior of metal soap. Moreover, by using a lubricant containing graphite, it is possible to avoid the sliding part such as oil well pipe threads being confined to a narrow area such as a thread groove.
[0190] It is necessary to avoid the formation of secondary products in the form of bands due to the addition of graphite, which may cause burns when the threads are tightened and loosened.
[0191] The reason why it is difficult to form a band-shaped secondary product derived from graphite when the above range is limited is considered to be as follows.
[0192] When the overlapping playing cards are pressed with fingers and made to slide, the graphite is deformed in a way that slides laterally one by one. However, when graphite is present in the binder resin, the more graphite content in the film, the more the binder resin is integrated with the graphite and firmly connected to form a strip. This becomes the main cause of burns. The small intervals between the graphites and the large size of each graphite are the main reasons for the length of the strip-shaped secondary products. It should be noted that the small intervals between the graphites refer to the low density of graphite. Therefore, the graphite concentration of the present invention needs to be more than 0.5% and less than 5% (relative to the total weight of the solid lubricant). The lower limit is a necessary value for effectively utilizing the lubrication improvement effect of graphite. The upper limit is the value required to induce the strip-shaped secondary products to be flaked or powdered. In the case of less than 5%, it is a regulation based on experimental results, but it can be inferred that even if the individual graphites are deformed, it is difficult to connect to each other and become long strips. It is further preferred that the particle size of the graphite is preferably less than 5μm. When tightening and relaxing, the band-shaped secondary products may have the situation that the elongated graphites are connected to each other and the size of each graphite is larger than 5μm. In this case, the large elongated graphite monomer has a high tendency to form a long band structure. Therefore, the size of the graphite is set to suppress this situation. Moreover, when considering the solid lubricating film, the situation of about 5μm in the thin part cannot be denied. In this local part, if the size of the graphite is larger than the film thickness, the solid lubricating film itself is easily destroyed starting from the interface between the binder resin and the solid lubricant when tightening and relaxing. Therefore, it is also meaningful to avoid this situation.
[0193] The reason why the size of the metal soap is preferably set to 5 μm or less is the same as that of graphite, and is to prevent the solid lubricating film itself from being easily destroyed.
[0194] At the same time, since both the metal soap and graphite have fine structures, the contact area with the solvent increases, thereby increasing the drying point. Therefore, by making the size of the particles 5 μm or less, it also helps to achieve early drying.
[0195] The solid lubricating film of the present invention is a structure in which a binder resin, graphite and alkaline soap are uniformly incorporated into the binder resin. However, there is also a part composed of metal soap, graphite and alkaline soap distributed in a manner of adhering to the outermost layer. In short, these solid lubricants become the basis for achieving lubrication of oil well pipe threads. Metal soap is a dry lubricant as a monomer, and functions as a lubricant in a dry state. In addition, when the metal soap has slightly poor lubrication during tightening and loosening and has frictional heat, it functions in a semi-molten or molten manner to form a lubricating film at the necessary lubrication location. The present invention does not effectively utilize the effect of mixing oil and metal soap to form a grease-like state as an effective utilization method of metal soap.
[0196] In the case where lubrication properties that cannot be achieved by metal soap alone are required, the present invention can effectively utilize the lubrication property improvement effect of graphite. Graphite is a flat surface-shaped solid structure that is weakly bonded by van der Waals forces and stacked. When force (torque) is applied to graphite, the lubrication effect of flat surface sliding is effectively utilized. In the lubrication behavior limited to the thread groove of the oil well pipe as described above, a long ribbon-shaped secondary product is formed, and the content is studied in a way that does not cause burning, and the size is adjusted to the preferred range.
[0197] Like metal soap, alkaline soap sometimes exists in the binder resin as a dry lubricant to function. At the same time, alkaline soap combines with tiny moisture to become mucus. As a result, there is also the following purpose: to use the effect of alkaline soap to slide the oil well pipe thread that is always slightly tilted, and guide the thread to engage in a stable position. In the actual tightening of oil well pipe threads, there are situations such as Range-2 and Range-3 (8m and 12m respectively) being slightly tilted. As described later Figure 5 , Figure 3 The initial setting position of the oil well pipe thread, such as the symbol 1a (10) of (b), that is, the position where the pin thread is light and the engagement is maintained to a certain extent by manual tightening, is normal. Moreover, while tightening with a power tong that rotates several times, the thread is held until Figure 4 (b) It cannot be denied that the solid lubricating film is ground off more than necessary and damaged. In order to make the pin thread slide into the regular position of the sleeve thread, the solid lubricating film is avoided from being ground off more than necessary, and the function of guiding to the regular meshing position can also be effectively exerted. One of the characteristics of the present invention is that the lubrication of the metal soap body is improved by adding graphite, and then a small amount of alkaline soap is contained. Therefore, it is key to smoothly guide to the regular meshing position, that is, slide in.
[0198] At this time, depending on the amount of graphite added, the graphite forms a band-like structure along the thread groove, and it is necessary to find a way to prevent it from causing burns.
[0199] In the present invention, when the solid lubricant is dried to form a film, the reagent is designed based on two situations: the case where the solid lubricant is completely incorporated into the film and the case where it is mainly incorporated into the film but distributed on the film surface. The portion outside the film refers to the portion that is weakly attached to the film surface to the portion that is only on the outermost layer.
[0200] Metal soap and graphite have two contributions. That is, these solid lubricants have a portion that is separated from the film and contributes to lubrication individually and in combination, and a portion that contributes to lubrication as a secondary product integrated with the binder resin.
[0201] In the present invention, in order to achieve a high level of lubrication, as described above, the weight of the binder resin component composed of the water-based polymer (acrylic), the solid lubricant, and the water-based solvent is set as follows as a preferred range. That is, the lower limit of each is set to 30% or more, 10% or more, and 40% or more, and the upper limit of each is set to 40% or less, 20% or less, and 50% or less, relative to the weight of all the components.
[0202] It is important here that the above-mentioned graphite is made to be more than 0.5% and less than 5% of all solid lubricants in terms of weight ratio relative to the total amount of solid lubricants. The lower limit is set to 0.5% in order to maintain high lubrication without forming a band-shaped secondary product as described above. In addition, if it is at this level, it can also be homogeneously mixed in a solvent dominated by water. The upper limit of 5% or less is to avoid the disadvantages caused by too much graphite. If it exceeds this range, in addition to the viewpoint of lubrication, the dissolution of graphite into the aqueous solvent cannot be carried out smoothly. In this case, the possibility of becoming agglomerates due to the convergence of graphite will increase anyway. In addition, the situation that it cannot be well deployed in the aqueous solvent occurs. Regarding alkaline soap, it is also necessary to mix 1% as the upper limit. The reason is to make it easy to guide the meshing position to the regular thread.
[0203] Next, conditions corresponding to the missing portion of the maintenance portion when graphite is buried for repair will be described.
[0204] After curing with a grinder or sandpaper, apply the reagent of the present invention to repair minor burns when the thread is burned.
[0205] At this time, in the state after maintenance, sometimes the solid lubricating film disappears, or part of the solid lubricating film is missing, or the metal of the threaded part is also ground and disappears. For example, there may be a situation where the thickness of 1 to 2 mm level disappears. Therefore, first of all, in order to achieve the purpose of filling this part, in the present invention, although the above-mentioned component regulations are the same, the weight of the water-based polymer (acrylic), the solid lubricant and the water are respectively set as the lower limit values relative to the weight of all the constituent components as follows. That is, as the respective lower limits, it is set to more than 30%, more than 10%, and more than 40%. In addition, as the respective upper limits, it is set to less than 40%, less than 20%, and less than 50%.
[0206] The solid lubricant is a component that is mainly composed of metal soap and graphite and alkaline soap. The binder resin is a water-soluble or water-dispersible binder resin that dissolves in a water-based solvent. The reagent can be applied with the part to be ground as the center, and the other parts can be applied thinly in the same way. The burnt part is physically buried by the coating. Once tightening and loosening are performed, the buried part is pressed from above. As a result, the part that was ground and maintained ends up being buried by the reagent.
[0207] In addition, by adjusting the viscosity of the coating agent to 1000 mPa·s or less, a high fluidity state such as that of the defective portion can be ensured. The viscosity is achieved by increasing the composition of the aqueous solution, etc. However, if the viscosity exceeds this range and is high, it is difficult to achieve the purpose of assisting lubrication or being able to repair a slightly burned portion. Therefore, considering this point, the above-mentioned concentration range is adjusted.
[0208] In addition, the solid lubricating film and coating agent of the present invention are evaluated by an evaluation method that conforms to the environment used in actual wells, and the upper and lower limits of the parameters are defined. Thus, lubrication assistance or repair of slightly burned parts that can be tolerated even in actual wells can be performed.
[0209] Here, in the case of the evaluation using only a short pin of about 1m, it is not an evaluation method according to the actual use conditions, so it is necessary to study the evaluation method. In the evaluation using a short pin as shown in the previous patent literature group, even if the NG pin can be screened out, the OK pin cannot be screened out. This is because the evaluation using a short pin tends to be a mild evaluation compared to the actual well and the simulated well, which becomes significant in the case of lubrication using a solid lubricating film. As described above, in the case of a solid lubricating film, the solid lubricating film is sometimes inevitably ground. Moreover, if they form secondary products, they block the thread gap, and the tendency to burn becomes higher.
[0210] In the conventional evaluation using short pins, there is a tendency to be difficult to detect problems because the pin thread is lightweight and can be tightened straight. Figure 5 As shown, the initial setting position is always not advanced halfway, and the power tongs are used to tighten from such an inclined meshing state. Therefore, the solid lubricating film is easily worn away, resulting in a tendency to easily burn. The present invention determines the upper and lower limits of the parameters based on the confirmed operation under such conditions in the actual well, and it is expected to be accurate. Considering the experimental cost and time, it is not appropriate to evaluate with the actual well and the simulated well every time.
[0211] In the present invention, the evaluation is replaced by a method called evaluation using a weight clamp. It should be noted that the method called evaluation using a weight clamp is an evaluation method invented by the present inventor. The evaluation method can include applying the deadweight of a pin of a harsh actual length in an actual well, and evaluating the effect of damaging the solid lubricating film by setting it in an offset state. The accuracy of the parameters of the present invention is provided by this evaluation.
[0212] This evaluation method is to install a weight of about 1 to 3 actual length pins on the upper end of the short pin. In addition, the initial setting position of the thread is set to a state where the pin thread is exposed about halfway relative to the sleeve thread. Then, a weight is applied during tightening, and no weight is applied during loosening, simulating tightening in an actual well. The device is shown in FIG. Figure 6 and Figure 7 The structural example will be described later.
[0213] In the present invention, parameters are defined based on evaluation using this new device structure, thereby ensuring lubrication performance that can withstand use in an actual well.
[0214] Effects of the Invention
[0215] According to the present invention, as a coating agent for repairing the threaded portion of an oil well pipe and improving lubrication, it is possible to provide an agent that does not use MoS 2 and is environmentally friendly and can withstand use in actual wells. BRIEF DESCRIPTION OF THE DRAWINGS
[0216] Figure 1 It is a figure which shows an oil country pipe and an oil country pipe threaded joint.
[0217] Figure 2 FIG. 1 is a diagram showing a tightening diagram in a conventional laboratory test (a) and FIG. 1 is a diagram showing an initial setting position at that time (b).
[0218] Figure 3 FIG. 1 is a diagram showing the actual tightening in a well (a) and FIG. 1 is a diagram showing the initial setting position at that time (b).
[0219] Figure 4 This is a diagram simulating the tightening state of an oil well pipe threaded joint.
[0220] Figure 5 It is a schematic diagram illustrating a state of a combination of a pin thread and a sleeve thread (the description of thread teeth etc. is omitted).
[0221] Figure 6 This is a diagram illustrating the conditions (weight pliers) of a new laboratory test (the description of thread etc. is omitted).
[0222] Figure 7This is a diagram showing an example of the setting of a weight under the conditions of a new laboratory test (weight clamp). Figure 7 In the description, the description of thread teeth etc. is omitted. DETAILED DESCRIPTION
[0223] Next, embodiments of the present invention will be described.
[0224] (constitute)
[0225] <Reagents>
[0226] The reagent of this embodiment is a reagent for imparting lubricating properties to the metal surface of metal parts such as oil well pipes. The reagent has solid lubricants, binder resins and solvent components as main components. Main components refer to, for example, the balance being materials that are inevitably added, or the solid lubricants, binder resins and solvent components accounting for 95% or more of the total weight.
[0227] [Solvent ingredients]
[0228] The solvent component contains water as a main component, and a lower alcohol having 3 or less carbon atoms is added to the water as an additive.
[0229] The volume of the additive relative to water is 100 or less and 10 or less relative to the volume of water.
[0230] More than 95% of the volume of the solvent is composed of the water and the additives.
[0231] As the above-mentioned additive, aqueous ammonia may be further added.
[0232] The solvent preferably accounts for, for example, 40% to 50% of the total weight of the reagent.
[0233] As the solvent, for example, at least a lower alcohol having a carbon number of 3 or less in a lower alcohol having a carbon number of 3 or less and ammonia water are added.
[0234] The volume of the lower alcohol having 3 or less carbon atoms is 0.5 or more and 10 or less relative to the volume 100 of water constituting the solvent. The volume of the ammonia water is 0 or more and 5 or less relative to the volume 100 of water constituting the solvent.
[0235] Examples of the lower alcohol having 3 or less carbon atoms include one or more lower alcohols selected from methanol, ethanol, isopropanol, n-propanol, and industrial ethanol.
[0236] [Solid lubricant]
[0237] The solid lubricant contains graphite and metal soap, which account for more than 95% of the weight of the entire solid lubricant component.
[0238] The solid lubricant is preferably contained in an amount of 10% to 20% of the total weight of the reagent. The main component of the solid lubricant is a metal soap. That is, the metal soap is contained in a larger amount than graphite in terms of weight ratio.
[0239] The graphite is set to be, for example, 0.5% or more and 5% or less of the total solid lubricant by weight. A more suitable range is preferably 1% or more and 3% or less. When the lower limit is set to 1% or more and the upper limit is set to 3% or less, the lubrication improvement effect brought by the graphite can be further expected, and it is easier to further avoid the formation of secondary products with a band structure.
[0240] In addition, alkaline soap is added at 1% or less, including zero. Lubrication behavior is achieved in the same manner as metal soap and graphite. In addition, as a further effect, alkaline soap also effectively functions to slide into the proper meshing position of the pin thread and the sleeve thread.
[0241] In addition, as a preferred range, the particle size of the metal soap and graphite is preferably 5 μm or less, for example, to prevent the solid lubricating film from being easily damaged during tightening and loosening, and to facilitate early drying by setting the particle size to a fine size.
[0242] Metal soap and alkaline soap are described. The former includes one or more soaps, and the soap includes a compound (metal soap) formed by a fatty acid of the following group A and a metal element (metal ion) of the following group B. The latter includes a compound (alkaline soap) formed by a fatty acid of the following group A and a metal element (metal ion) of the following group C.
[0243] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0244] Group B: Mg, Ca, Zn, Ba;
[0245] Group C: Na, K.
[0246] [Binder resin]
[0247] The binder resin is a water-soluble or water-dispersible polymer, and is a polymer or copolymer containing 90% or more of a monomer belonging to acrylate or methacrylate in terms of the weight of the entire binder resin.
[0248] The binder resin is set to, for example, 30% to 40% of the total weight of the reagent.
[0249] The water-soluble or water-dispersible polymer constituting the binder resin is, for example, a polymer composed of a monomer among the monomers described in (1) to (4), or a copolymer containing two or more monomers.
[0250] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0251] (2) Monomers that integrate acrylic acid esters, methacrylic acid esters and their derivatives with monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters and their derivatives;
[0252] (3) A monomer grafted with the above (1) or (2);
[0253] (4) A monomer composed of one or both of a vinyl compound and a urethane compound and at least one of the monomers (1) to (3) integrated together.
[0254] Regarding the reagent, the viscosity of the reagent is 1000 mPa·s or less.
[0255] The reagent has a concentration of 1 mg / mm on the metal surface. 2 When the coating amount is applied and left to dry in a windless atmosphere at room temperature, the early drying property is that the coating can be dried within 30 minutes. Here, drying at room temperature in the atmosphere means drying at room temperature (15-30°C, for example, 24°C).
[0256] <Method for producing reagent>
[0257] Regarding the reagent, the metal soap is dispersed in a lower alcohol to make it turbid, and then added to water as a solvent to prepare the metal soap.
[0258] <Oil Well Pipe Repair Method>
[0259] The invention relates to an oil well pipe repairing method for repairing the lubricating film of the threaded portion of the oil well pipe.
[0260] After curing the burned area in the threaded portion of the oil well pipe, the coating agent of the present invention is applied to at least the cured portion, thereby filling the ground area with a film containing graphite to repair it.
[0261] <Methods to improve lubrication of oil well pipes>
[0262] The coating agent of the present invention is applied to the existing lubricating film formed on the threaded portion of the oil country tubular good, thereby improving the lubricating performance.
[0263] <Oil Well Tubular Goods and Oil Well Tubular Goods Threaded Joints>
[0264] Oil well pipe is Figure 1 The sleeve 2 shown has an internal thread 2a and the pin 1 has an external thread 1a.
[0265] like Figure 1As shown, the oil well pipe threaded joint is composed of a sleeve 2 such as a coupling having an internal thread 2a and a pin 1 having an external thread 1a. In addition, a lubricating film having a solid lubricating film of the present invention is formed on the contact surface (fastening surface 10) of the threaded portion of at least one of the sleeve 2 and the pin 1.
[0266] A lubricating film having a solid lubricating film is formed on the threaded portion of the oil country tubular good of the present embodiment.
[0267] The solid lubricating film includes a binder resin and a solid lubricant dispersed in the binder resin.
[0268] The solid lubricating film has a solid lubricant dispersed in a binder resin as a matrix component.
[0269] The solid lubricant contains graphite and metal soap, and the graphite and metal soap account for 95% or more of the weight of the entire solid lubricant component.
[0270] The particle size of graphite is, for example, 5 μm or less, and the particle size of the metal soap is, for example, 5 μm or less.
[0271] The metal soap is contained in an amount of, for example, 0.5% to 5% by weight of the entire solid lubricant.
[0272] The metal soap includes, for example, one or more metal soaps including a compound formed of a fatty acid selected from the following Group A and a metal element (metal ion) selected from Group B.
[0273] The alkaline soap includes, for example, one or two or more alkaline soaps including a compound formed of a fatty acid selected from the following Group A and a metal element (metal ion) selected from Group C.
[0274] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0275] Group B: Mg, Ca, Zn, Ba;
[0276] Group C: Na, K.
[0277] The binder resin is a water-soluble or water-dispersible polymer, and is a polymer or copolymer containing 90% or more of a monomer belonging to an acrylate or methacrylate, with the weight of the entire binder resin as the denominator.
[0278] The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of a monomer among the monomers described in (1) to (4), or a copolymer containing two or more monomers.
[0279] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0280] (2) Monomers that integrate acrylic acid esters, methacrylic acid esters, and their derivatives with monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters, and their derivatives;
[0281] (3) A monomer grafted with the above (1) or (2);
[0282] (4) A monomer composed of one or both of a vinyl compound and a urethane compound and at least one of the monomers (1) to (3) integrated together.
[0283] The film thickness of the solid lubricating film is 10 μm or more and 100 μm or less, and the solid lubricating film is soft with a film hardness of B or less in pencil hardness. The film thickness refers to the so-called crown part (thread tooth equivalent part) of the surface of the thread tooth part, which can be measured by ultrasound or the like in a non-destructive manner. In particular, the oil well pipe thread refers to the thread part (flat part) of the thread that can be used as a high-grade joint, which is a barb type in the sleeve thread and a hook type in the pin thread. The film thickness is not the longitudinally erected part of the thread tooth on the rolling tooth side and the load tooth side.
[0284] Furthermore, a base film (not shown) such as a Mn phosphate chemical conversion treatment film, a plating film, etc. may be provided under the solid lubricating film.
[0285] The oil country pipe of at least one of the sleeve and the pin is formed of the oil country pipe having a lubricating coating formed thereon according to the present invention.
[0286] When the oil country pipe of one of the sleeve and the pin is the oil country pipe having a lubricating film formed thereon according to the present invention, it is preferred that a film having a higher hardness than the solid lubricating film be formed on the threaded portion of the other oil country pipe.
[0287] As described above, the reagent of the present invention is a coating reagent composed of a water-soluble or water-dispersible polymer (aqueous polymer) as a binder resin, a mixed system of metal soap and graphite as a solid lubricant, and a solvent composed mainly of water.
[0288] The agent of the present invention is effectively used as a solid lubricating film for oil well pipe threads. At the same time, for example, the agent of the present invention is also used when it is necessary to further improve the lubricity of an already formed solid lubricating film. For the purpose of improving lubricity or for the purpose of avoiding burning including preventive significance, the agent of the present invention can also be applied to an already existing solid lubricating film.
[0289] In addition, for example, in a thread consisting of a thread portion and a sealing portion, it is used when only a slight burn occurs in the thread portion. That is, when a local repair is performed at a well site, the agent of the present invention is applied to the surface to be repaired after curing. Thus, the oil well pipe and oil well pipe threaded joint of the present invention are formed.
[0290] The parameter groups shown below are set in association with each other for the required characteristics, and are realized within the upper and lower limits specified in the present invention.
[0291] First, the required characteristics to be targeted are described, and then the specified ranges of each parameter and their meanings are explained.
[0292] It should be noted that the present invention is intended for lubrication assistance and lubrication during restorative local repair. Therefore, it is not particularly intended for corrosion resistance. Corrosion resistance is achieved by the existing solid lubricating film, and in restorative local repair of a well site, tightening is performed immediately after the repair, so only lubrication is targeted.
[0293] (Regarding the targeted lubrication properties, lubrication assist properties, and repair of lightly burned parts)
[0294] When the solid lubricating film of the oil well pipe thread intended by the present invention is effectively utilized, the judgment is made based on the lubricating properties of the solid lubricating film, and the film is gradually consumed, which is unique to the solid lubricating film. Then, the lubrication performance is judged by a slightly different standard from the provisions of API-5C5, ISO13679, etc. The casing size uses the tightening and loosening times of more than 2 times as the qualified judgment standard, and the pipe size uses the tightening and loosening times of more than 5 times as the qualified judgment standard. As described above, the confirmation of its characteristics is based on the premise of confirming it by a new evaluation method that can simulate the actual well.
[0295] In the evaluation of the properties as a lubrication aid, the lubrication properties that increase the number of tightening and loosening times that can be achieved by the threaded joint by applying the coating agent of the present invention by more than one time are judged to have a good effect. Lubrication aid refers to the improvement of lubricity by applying the agent of the present invention to the entire surface of the solid lubricating film that has been set on the threaded portion. In most cases, the goal is to increase the number of tightening and loosening times by 2 to 3 times or more, but the lubrication aid is considered good (qualified) as long as it can increase the tightening and loosening by more than one time. It should be noted that the judgment is based on the lubrication properties of the solid lubricating film that has been attached. Therefore, the benchmark of "casing size is more than 3 times" used in the provisions of API-5C5, ISO13679, etc. is not used. Similarly, confirmation through actual well simulation evaluation is a prerequisite.
[0296] Regarding the repair of the slightly burned part, for example, the burned part is limited to the burn of the thread part, and the burn of the sealing part is not included.
[0297] Repairing is performed to ensure lubrication again after the burned part has been cured using a grinder, a file, sandpaper, etc. Specifically, the repairing is performed by applying the agent of the present invention to only the periphery or the entire surface including the burned part.
[0298] If it is possible to tighten more than one time from the burned state, it is considered good (qualified). Furthermore, if it is possible to tighten directly more than one time (more than two times in total), it is considered even better. Regarding the evaluation of the repair of the slightly burned part, the evaluation method is also based on the premise of confirming it through the above-mentioned new evaluation method that can simulate the actual well.
[0299] In this simulation, after loosening the tightening in the actual well simulation once, physical damage was applied and the portion was intentionally cured with a grinder, file, sandpaper, etc. Then, the agent of the present invention was applied to perform repair and restoration.
[0300] (Regarding the early drying property as a target)
[0301] The present invention uses an aqueous solvent, but aims to achieve early drying of the applied reagent by the following means. That is, the volatility of lower alcohols and ammonia is effectively utilized, and the blending range and size management of metal soap and graphite are set. Furthermore, the metal soap and graphite are prevented from forming lumps. In addition, the method of introducing the solid lubricant into the binder resin is changed.
[0302] The level of early drying is judged based on two criteria.
[0303] The first criterion is whether or not the above-mentioned design can be used to achieve faster drying. If the drying is done in the open air, the comparison is done in the open air. If the drying is done by air, the comparison is done by aiming for early drying. The location / position of the comparison is also evaluated at the same location.
[0304] The second criterion is whether it can be dried within 5 minutes, more preferably within 1 minute, in the drying with air supply (non-heating). When drying outdoors or indoors at room temperature, the goal is to be able to dry within 30 minutes or less, preferably 15 minutes, and more preferably within 5 minutes. The drying mentioned here refers to a semi-cured level or a cured drying level that exceeds the dry to touch level. It should be noted that the coating terms such as dry to touch and semi-dry are defined in accordance with JIS K5500-2000. However, the air supply in the non-heating and atmospheric environment is based on the results confirmed in an environment of 14-18°C in the research of the present invention.
[0305] Specifically, the coating amount on the metal surface was set to 0.1 g / mm 2When the air is left to dry, it is preferred to have a moderate early drying property that can be dried within 30 minutes at room temperature. The early drying property also includes the following detailed description and is a level that can be achieved by the parameter group specified in the present invention. Thus, drying can be performed earlier by air drying or warm air drying.
[0306] In the present invention, a coating agent prepared so as to have low viscosity and high fluidity is used.
[0307] Regarding their evaluation positions, when the oil well pipe thread is placed horizontally and a water-based acrylic adhesive resin-based water-based coating is applied, there is a tendency for the liquid to drip along the thread groove and accumulate at the 6 o'clock position. Therefore, there is a tendency for the drying of this part to be slightly slower, so the place for comparative evaluation is set to compare the drying from 9 o'clock to 3 o'clock. In the case of coating with the oil well pipe thread upright, in the case of the pin thread, the part that directly falls falls to the ground, so it will not accumulate particularly. However, sometimes a water drop-shaped droop is formed at the front end of the pin. In this case, this part is excluded to evaluate the drying time. In the case of the sleeve thread, it droops downward in the same way. However, in the case of the high-grade joint, the tendency to accumulate in the height difference of the shoulder part cannot be said to be zero, so this part is excluded to discuss the drying time.
[0308] In addition, there are physical depressions in the parts of the actual burn site that have been maintained, and the reagent of the present invention is also applied for the purpose of filling this part. Therefore, only the dry state of the surface can be discussed. The drying time of the parts without problems in the above parts is evaluated to discuss the early drying property.
[0309] The reason why early drying is required is that, as the most stringent condition, it is assumed that the coating agent and the solid lubricating film using the coating agent are used for repair work due to a fault such as a slight burn at a well site. Therefore, it is intended to repair the problem area by grinding it with a file, abrasive paper, etc., and then repair it with the coating agent of the present invention. Repairing with a coating agent means filling the repaired part and ensuring lubrication. Therefore, it is assumed that it is used under the premise of strictly prohibiting fireworks and cannot use practical applications related to drying, and early drying is intended in drying by air supply.
[0310] (Methods for achieving early drying)
[0311] The present invention uses an aqueous solvent and achieves early drying by the following method. That is, the volatility of lower alcohols and ammonia is effectively utilized. In addition, the setting range and size management of the metal soap and graphite are performed. Furthermore, research is conducted to prevent the metal soap and graphite from forming lumps, and the method of taking the solid lubricant into the binder resin is changed. Thus, early drying is sought.
[0312] The details are described below for each item, and the overall outline and design concept of the coating agent are described.
[0313] The reagent of the present invention contains a lower alcohol.
[0314] Regarding the inclusion of lower alcohol, the concentration is adjusted so that the reagent has a flash point of 60°C or higher or is considered non-flammable in order to enable use in an environment where fireworks are strictly prohibited. The volatility of the lower alcohol is then utilized to achieve early drying.
[0315] It should be noted that the reagent of the present invention does not use diluent-based VOCs. This is to comply with the strict prohibition of pyrotechnics at the well site, the safety and hygiene of the workers, and to avoid the installation of exhaust equipment such as ventilation so that the work can be carried out.
[0316] Depending on the situation, the volatility of aqueous ammonia is also effectively utilized in the reagents to control their concentration within an appropriate range at a level that can be used without using ventilation equipment.
[0317] In addition, the concentration and particle size of the metal soap and graphite contained are controlled within an appropriate range to achieve early drying. Specifically, a size with a small average particle size is selected, and the concentration is adjusted to an appropriate amount. In this way, the total surface area of the solid lubricant is increased, and the volatilization of lower alcohols and ammonia is effectively utilized to achieve early film formation.
[0318] The size (average particle size) of the metal soap and graphite is 5 μm or less, preferably 1 μm or less. Thus, the surface area of the solid lubricant is increased and drying is enhanced. At the same time, when tightening and loosening, the damage to the solid lubricating film that is easily damaged from the interface between the binder resin and the metal soap and graphite can be reduced. If it exceeds 5 μm, the solid lubricant may be distributed through the film in the longitudinal wall-shaped part where the solid lubricating film is easy to become thin, so it is easy to be damaged. The longitudinal wall-shaped part is, for example, the part on the rolling tooth side and the load tooth side.
[0319] In addition, when the solid lubricant is dissolved, the metal soap itself and the graphite itself are combined to form a mass, and it is necessary to take measures to prevent the apparent size from exceeding the size of each other and becoming larger. In order to avoid the formation of the mass, the metal soap and graphite are temporarily dissolved in a lower alcohol and then mixed into a mixed solution of a solvent composed of water and an aqueous polymer.
[0320] The metal soap also functions as a main component of the lubricant. Similarly, the graphite functions to support the lubricant and also has the function of filling the concave portion formed on the repaired surface during restorative repair.
[0321] The viscosity of the coating agent is adjusted to 1000 mPa·seconds or less, so that the agent is not applied thickly. In short, as a reagent, it is intended to be a low viscosity, dry liquid viscosity. The lower limit of the viscosity is not set, but it is about 40 mPa·seconds or more. When a water-soluble or water-dispersible polymer material is added and the aqueous solution is prepared, the viscosity should not be 1 mPa·second, which is the viscosity of water, but higher. As a result, its level is about 40 mPa·seconds or more.
[0322] (Basic composition of a coating agent used to assist lubrication or repair minor burns)
[0323] The reagent is mainly composed of a solid lubricant, a binder resin, and a solvent that does not remain in the film after the reagent is applied.
[0324] The solvent is mainly water. One or two or more lower alcohols having a carbon number of 3 or less are further added to the water as additives. Depending on the situation, ammonia water may also be added as the additive.
[0325] The volume of the additive is set to be 10 or less relative to the volume of water (100). The total volume of water and the additive is set to be 95% (volume / volume %) or more of the volume of the entire solvent.
[0326] The main components of solid lubricants are graphite and metal soap. The main components refer to the total weight of graphite and metal soap accounting for more than 95% of the weight of all solid lubricant components.
[0327] The binder resin has a water-soluble or water-dispersible polymer as a main component. Among the polymers, polymers and copolymers composed of monomers belonging to acrylates and methacrylates account for 90% or more of the weight of the entire binder resin component.
[0328] As described above, the basic composition of the present invention includes a solvent mainly composed of water, a solid lubricant mainly composed of graphite + metal soap, and a binder resin mainly composed of a polymer composed of monomers belonging to acrylates and methacrylates and a copolymer thereof. In terms of each component unit, the main component refers to more than 95%, more than 95%, and more than 90%, respectively. In short, it means that if a small amount of impurities, unavoidable mixtures, and nasal medicines are mixed, it is acceptable.
[0329] If these criteria are not met, the stability of the film formed by coating the reagent is reduced, and the expected properties of the present invention may not be achieved. It should be noted that in the film state, the solvent also includes alcohol, ammonia, etc., which volatilizes / evaporates without remaining in the film.
[0330] The polymer composed of monomers belonging to acrylate and methacrylate itself becomes a dry film (matrix). The film is a film in which a solid lubricant of metal soap and graphite is uniformly retained in the film (matrix). A part of the solid lubricant is in a state of being attached to the surface layer of the film (matrix), or a part is buried in the film (matrix) and a part is exposed on the surface.
[0331] It should be noted that the effective use of lower alcohol and ammonia is to be added for the purpose of homogeneous dissolution of the metal soap and early drying of the film by effectively utilizing volatility.
[0332] (Binder resin, solid lubricant, water mixing ratio)
[0333] In the present invention, about the mixing ratio of binder resin, solid lubricant, water, binder resin (water-soluble or water-dispersible polymer), solid lubricant (metal soap and graphite), solvent as water main body of solvent preferably has the following value as lower limit respectively. That is, preferably more than 30%, more than 10%, more than 40% respectively. In addition, as respective upper limit, preferably be deployed to less than 40%, less than 20%, less than 50%. It should be noted that, as a whole, deploy coating reagent in a manner that they are 100%.
[0334] Water has no environmental problems at all. For this reason, water is selected as the main component of the solvent. Water as the solvent volatilizes / evaporates during film formation and is separated from the film.
[0335] In order to achieve early drying of the film, it is generally believed that the less water there is, the easier it is to dry. However, this is not actually the case. In the case of low water content and high viscosity, it is often difficult to dry.
[0336] The present invention uses the solid lubricant in the amounts and sizes listed below, a low-grade alcohol that is volatile but has few problems, and aqueous ammonia. However, the most important thing is to be able to apply the reagent thinly.
[0337] Therefore, although the details will be described later, the viscosity of the coating agent is reduced to improve its fluidity and to apply it thinly. Therefore, in the present invention, in order to reduce the viscosity, as described above, it is preferred to add 40% or more of water.
[0338] Meanwhile, the water content is an amount sufficient to contain a necessary amount of water-soluble or water-dispersible polymer. The upper limit of water is set to 50% or less for the following reason: if the upper limit is exceeded, the binder resin itself becomes too thin and the viscosity becomes too low, so that the required amount of the agent cannot be applied.
[0339] The water-soluble or water-dispersible polymer refers to a polymer mainly composed of a water-based acrylic (methacrylic) resin, and is preferably formulated to be 30% or more and 40% or less.
[0340] The purpose of this range is to ensure early drying properties by making the viscosity within an appropriate range, to mix and retain the solid lubricant in the binder resin film, and to position the solid lubricant monomer at a position that is also attached to the surface side of the solid lubricating film. When the viscosity is less than 30%, the liquid viscosity of the reagent is too low, the fluidity increases, and the solid lubricating film becomes thinner, thereby failing to maintain the lubricating properties of the film. When the viscosity exceeds 40%, the viscosity of the reagent increases, and depending on the coating method, the film becomes locally thicker, and the possibility of achieving early drying properties increases. In addition, the film becomes uneven, and there is a situation where the lubricating properties are deteriorated.
[0341] Solid lubricants have metal soap and graphite as main components, and the main component is metal soap, that is, they contain more metal soap than graphite.
[0342] The reason for setting the content of solid lubricant to a preferred range of more than 10% and less than 20% is also to satisfy the appropriate range set for the composite factors at the same time. It is set to more than 10% because if more than necessary solid lubricant is not added, the target lubrication cannot be achieved. In addition, it is also to ensure the surface area and amount of the solid lubricant described later, and to expect the effect of promoting early drying. In addition, it is set to less than 20% to avoid the disadvantages caused by too much graphite. This is because, if it exceeds this range, although it is also linked to the amount of water-based acrylic acid, the secondary products formed during lubrication become ribbon-shaped, and its fragments are blocked in the thread gap, and the possibility of burns increases. At the same time, in any case, the possibility of becoming agglomerates due to the convergence of graphite increases, and the lubrication itself deteriorates or cannot be well allocated to a water-based solvent.
[0343] Here, the solvent evaporates and disappears, so that what remains as a solid lubricating film formed on the thread surface is the solid lubricant and the binder resin.
[0344] Therefore, in order to achieve the properties of a solid lubricating film, it is important to mix the weight ratio of the binder resin to the solid lubricant so that the weight ratio of the solid lubricant is between 0.25 and 0.66 relative to the weight of the binder resin, while dissolving in the above-mentioned water-based solvent. A weight ratio range of 0.3 or more and 0.5 is more preferred. The material of this ratio results in the formation of a solid lubricating film on the thread surface.
[0345] In order to uniformly disperse the solid lubricant in the binder resin, there is a limit in terms of lubrication improvement. If the solid lubricant is too much, it cannot completely enter the film and only adheres to the surface, which is not conducive to fully achieving lubrication improvement. Therefore, as a preferred range, the upper limit is 0.5. On the contrary, if it is too little, it becomes a situation where there is little solid lubricant required for lubrication, and the lubrication target level cannot be maintained. Therefore, the preferred lower limit is 0.3.
[0346] (Effective utilization of lower alcohols, effective utilization of ammonia water)
[0347] As a solvent component other than water, 0.5 to 10 of one or more lower alcohols having carbon atoms of 3 or less are added per volume 100 of water. Furthermore, 0 to 5 of ammonia water may be added per volume 100 of water.
[0348] The lower alcohol having 3 or less carbon atoms is preferably at least one lower alcohol selected from methanol, ethanol, isopropanol, n-propanol, and industrial ethanol.
[0349] Lower alcohol is one of the means for promoting early drying. It is envisaged that the reagent of the present invention is used in the restorative repair of the well site. Therefore, under the most stringent conditions, the reagent needs to be used under the strict prohibition of fireworks. In addition, in order to consider the safety and hygiene of the operator, it is preferred not to use organic solvents of the diluent system represented by toluene, xylene, and benzene and to prevent the flash point of the reagent from being reduced. Therefore, a lower alcohol with a carbon number of 3 or less is used.
[0350] Although described in detail below, in order to make the flash point of the reagent 60° C. or above or to make it non-flammable, it is necessary to limit the upper limit of the concentration of these lower alcohols and adjust the flash point of the reagent to a higher level.
[0351] When these lower alcohols are composed of 100% each, they have a flash point of 10 to 15°C and a boiling point of about 65 to 100°C. Therefore, it is necessary to mix the lower alcohols with water as a solvent, a binder resin, and a solid lubricant so that the reagent has an appropriate flash point. In addition, mixing a large amount of lower alcohols to promote early drying of the reagent is dangerous in an environment where fireworks are strictly prohibited.
[0352] The lower limit (0.5 or more relative to 100 volumes of water) is the minimum limit for effectively utilizing volatility, while the upper limit (10 or less relative to 100 volumes of water) is set as the permissible upper limit for adjusting the flash point.
[0353] Ammonia water is sometimes added in order to adjust the pH at which the water-based polymer can stably exist. Therefore, ammonia water can also be added in a manner that becomes the upper limit region of the pH range specified by each water-based polymer, thereby effectively utilizing the volatilization of the ammonia. The reason why the upper limit of the addition of ammonia water is set to 5 or less relative to the volume 100 of water is as follows. That is, in fact, it is an upper limit value set in order to add only about 5 or less. Usually, relative to the volume 100 of water, most of the upper limits are 1 to 2.
[0354] In this specification, ammonia water is expressed in the form of concentrated ammonia water (containing 28-30% ammonia). When using dilute ammonia, it is replaced by the value converted by dividing according to the mixing ratio of concentrated ammonia water.
[0355] The lower alcohols having 3 or less carbon atoms include methanol, ethanol, isopropanol, n-propanol, and industrial ethanol. The reason why alcohols having 4 or more carbon atoms are not included is that their solid solubility in water is slightly reduced.
[0356] At the same time, the lower alcohol has the function of preventing the metal soap as a solid lubricant from agglomerating and preventing the metal soap from being directly agglomerated at the size at the time of addition and being formulated.
[0357] If only dissolving metal soap in water, then also be affected by having water repellency, metal soap will not be mixed into water, and will meet each other and become agglomerates.Even if the particle diameter of metal soap below the specified value is mixed into the reagent with great difficulty, if metal soap is directly mixed into water, then can not be fully dispersed.Therefore, even in the state of becoming film, metal soap will not be homogeneously introduced into the binder resin, but will become a biased film, and lubrication is not good.Therefore, the material of the state that lower alcohol and metal soap are mixed should be adopted to be mixed in the dispersion liquid of water-soluble or water-dispersible polymer and water.At this moment, the concentration of lower alcohol and the content of metal soap need to be adjusted to fall within the scope specified by the present invention.
[0358] (About solid lubricants such as graphite and metal soap)
[0359] The average particle size of graphite is set to 5 μm or less, and the average particle size of the metal soap is set to 5 μm or less.
[0360] In addition, in the solid lubricant, the weight ratio of graphite is set to 0.5% or more and 5% or less, and the remaining main component is metal soap. At the same time, the upper limit of alkaline soap can be set to 1% and contained.
[0361] In the present invention, the metal soap is mainly made to have lubricity, which is further improved by graphite. Alkaline soap can also be expected to have a lubrication improvement effect. However, as a further effect brought by the alkaline soap, there are the following functions. That is, the alkaline soap effectively functions when guiding the deviation of the initial meshing position of the pin thread and the sleeve thread to slide into the regular meshing position. The alkaline soap is particularly effective even in the presence of a little moisture. Moreover, the alkaline soap has the effect of effectively sliding it to the meshing position of the regular thread even when the thread teeth are wet in the presence of rainfall or backflow from the well.
[0362] The regulation of the size of the solid lubricant is one of the means for promoting early drying. In particular, for metal soaps and graphite, which are water-insoluble solid lubricants, early drying is achieved by increasing the contact surface area with the solvent by reducing the particle size, and by effectively utilizing the volatility of lower alcohols and ammonia.
[0363] The smaller the particle size of graphite and metal soap, the better. Preferably, the size is less than 1 μm. In the case of exceeding 5 μm, a solid lubricant with the same film thickness as when it becomes a solid lubricating film appears. In addition, if it is not embedded in the film thickness, there is also a situation where the film is easily damaged when the oil well pipe thread is tightened and loosened. From this point of view, it needs to be less than 5 μm. In the present invention, as described later, with respect to the film thickness, 10 μm or more and 100 μm or less are specified as the preferred range. If the particle size of graphite and metal soap is less than 5 μm, preferably less than 1 μm, the possibility of the film being easily damaged can also be reduced when the oil well pipe thread is tightened and loosened.
[0364] As described above, the solid lubricant is mainly composed of graphite and metal soap. However, if the content is less than 5%, other substances may be mixed in as impurities as solid lubricants. For example, BN (boron nitride), mica, talc, MCA (melamine cyanurate), PTFE (polytetrafluoroethylene), and alkaline soap groups will not hinder the intended effect of the present invention as long as they are in a trace amount.
[0365] (A countermeasure to prevent the formation of band-shaped secondary products)
[0366] The tendency of band-shaped secondary products to form during tightening and loosening increases with the addition of graphite. The origin of the band-shaped secondary products is a structure formed mainly of graphite extending along the thread groove. In order to eliminate the lubrication improvement effect brought about by the addition of graphite, the band-shaped secondary products caused by graphite are formed longer, and when they are blocked somewhere in the thread gap, the possibility of burning becomes higher.
[0367] Since graphite is dispersed in the binder resin, it is impossible to deny the tendency to form a secondary product in the form of a strip. However, by changing the strip into a peeling flake, a fragment, or a powder, burning can be avoided.
[0368] When the overlapping playing cards are pressed with fingers and made to slide, the graphite is deformed in a way that slides laterally one by one. However, when graphite is present in the binder resin, the more graphite content in the film, the more the binder resin is integrated with the graphite and firmly connected to form a strip. This becomes the main cause of burns. The small intervals between the graphites (the existence density of graphite is low), and the large size of each graphite become the main reasons for the length of the strip-shaped secondary products. Therefore, the graphite concentration of the present invention needs to be more than 0.5% and less than 5% relative to the weight of the total solid lubricant. The lower limit is a necessary value for effectively utilizing the lubrication improvement effect of graphite. The upper limit is the value required to induce the strip-shaped secondary products to be flaked or powdered. When it is less than 5%, it is a regulation based on experimental results, but it can be inferred that even if the individual graphites are deformed, it is difficult to connect to each other and become long strips. If it exceeds 5%, the amount of strip-shaped secondary products from the solid lubricant in the binder resin and the graphite in the form of not entering the binder resin and adhering to the surface may become excessive. Therefore, a band-shaped secondary product consisting only of graphite is formed, and as a result, a strong band-shaped secondary product may be formed. Moreover, when tightening and loosening, it is blocked in the thread gap, and burning is inevitable.
[0369] It is further preferred that the size of the graphite is 5 μm or less. When the band-shaped secondary products are tightened and relaxed, when the individual stretched graphites are connected to each other and when the size of each graphite is larger than 5 μm, they have the following tendency. That is, the tendency of the long band structure caused by the elongated form of large graphite monomers is high. This is to suppress this situation by setting it to 5 μm or less. Moreover, when considering the solid lubricating film, it is impossible to deny the situation of about 5 μm in the thin part. Therefore, in this local part, if the size of the graphite is larger than the film thickness, the solid lubricating film itself is easily destroyed starting from the interface between the binder resin and the solid lubricant when tightened and relaxed. Moreover, by setting it to 5 μm or less, it is also meaningful to avoid this situation.
[0370] The reason why the size of the metal soap is preferably 5 μm or less is the same as that of graphite, and is to prevent the solid lubricating film itself from being easily destroyed.
[0371] At the same time, since both the metal soap and graphite have fine structures, the contact area with the solvent increases, thereby increasing the drying point. Therefore, by making the particle size 5 μm or less, it also contributes to early drying.
[0372] In the present invention, whether it is metal soap or graphite, it includes the presence of parts that contribute to lubrication alone and in combination and the solid lubricant distributed in a manner carried on the film. In order not to introduce a band-shaped secondary product formed mainly by graphite, it is adjusted to the above-mentioned concentration distribution and appropriate size. In order to achieve this, the weight of the binder resin, solid lubricant and water of the water-based polymer (acrylic acid) is respectively set to more than 30%, more than 10%, and more than 40% as the lower limit relative to the weight of all the constituent components. In addition, as the respective upper limits, it is set to less than 40%, less than 20%, and less than 50%.
[0373] Importantly, the solid lubricant is made to be more than 10% and less than 20% relative to the total weight of the reagent. Moreover, compared with graphite, most of the solid lubricant is a metal soap, and the weight of graphite relative to all solid lubricants (including: alkaline soap) is adjusted to an amount equivalent to more than 0.5% and less than 5%. Moreover, the lower limit is set to 0.5% in order to maintain high lubrication without forming a banded secondary product as described above. In addition, if it is this level, it is also possible to be homogeneously mixed in the water of the solvent. The upper limit of 5% or less is to avoid the drawbacks caused by too much graphite. This is because, if it exceeds the scope, the possibility of becoming a mass due to the convergence of graphite each other will become higher anyway, or it cannot be well deployed in the solvent of the water system, or the generation of banded secondary products becomes significant.
[0374] (Water-soluble or water-dispersible polymer constituting the binder resin)
[0375] The water-soluble or water-dispersible polymer constituting the binder resin is preferably a polymer composed of the following monomers (1) to (4), or a copolymer containing two or more monomers.
[0376] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0377] (2) Monomers that integrate acrylic acid esters, methacrylic acid esters, and their derivatives with monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters, and their derivatives;
[0378] (3) A monomer grafted with the above (1) or (2);
[0379] (4) A monomer composed of one or both of a vinyl compound and a urethane compound and at least one of the monomers (1) to (3) integrated together.
[0380] In the present invention, a water-soluble or water-dispersible polymer is used as a binder resin. In the present invention, it is of course assumed that the film is formed after water splashes (volatilizes / evaporates). Therefore, in a narrow sense, the binder resin refers to a synthetic polymer. Pectin, agar, starch materials, cellulose, and natural gum (alginate) materials that are well-known in natural polymers are excluded. In addition, the situation where semi-dry moisture is maintained in the stage of drying (scattering water) is also excluded. It should be noted that for substances that are not completely dried, the coated substance may induce corrosion in the case of carbon steel.
[0381] Specifically, in the present invention, the substance that meets the requirements of water-soluble or water-dispersible polymers includes substances composed of one polymer and copolymers containing two or more monomers. Each monomer corresponds to the monomers of (1) to (4) above. At least one polymer in (1) to (4), or any one or both of the copolymers containing two or more monomers, includes substances formed by copolymers with other compounds. Other compounds refer to monomers such as maleic acid, sulfonic acid, styrene, carboxylic acid and its salts. Polymers and copolymers containing acrylates and methacrylates in the basic structure are regarded as monomers belonging to acrylates and methacrylates.
[0382] The reason for selecting acrylate (acrylic acid) resin is that it is a general-purpose, easily available reagent and is easy to make a water-based polymer. In addition, it is widely used, and many reagents are registered in the chemical reagent regulations of various countries, and it is convenient to use. By mixing on the basis of appropriate regulations of acrylate and solid lubricant, a coating reagent with early drying properties, which can be used for lubrication assistance or repair of light burns, can be formed.
[0383] In the reagent of the present invention, the binder resin is dissolved in a solvent in which water accounts for the majority. Then, it is applied to make the water fly, that is, the water evaporates / volatizes to form a film. In addition, there is a basic policy of considering the environment. Therefore, it is designed without using raw materials containing heavy metals represented by lead and fluoroalkyl groups of the group called PFAS, which are considered to be problematic recently.
[0384] At the stage of finally becoming a film, it is preferred that the polymer or its copolymer contains more than 95% of monomers belonging to acrylates and methacrylates. It should be noted that, during copolymerization, the substance formed by copolymerization of monomers other than acrylates and methacrylates is regarded as a polymer of acrylates and methacrylates, satisfying the above-mentioned regulation of more than 95%. Setting it to more than 95% means that most of it is composed of acrylates and methacrylates. In addition, it means that even if less than 5% of other polymers are added, it can be allowed. In essence, as a copolymer, the actual situation is that the polymer of acrylates and methacrylates is close to 100%.
[0385] (Types of metal soap and alkaline soap)
[0386] The metal soap and the alkaline soap include a combination of one or more higher fatty acids and metal elements (metal ions). Each metal soap is preferably a compound formed by a fatty acid selected from the following Group A and a metal element (metal ion) selected from Group B. Each alkaline soap is preferably a compound formed by a fatty acid selected from Group A and a metal element (metal ion) selected from Group C.
[0387] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0388] ·Group B: Mg, Ca, Zn, Ba, Al;
[0389] ·Group C: Na, K.
[0390] The metal soap of the present invention is effectively used as a solid lubricant. The metal soap of the present invention is not used as a thickener for increasing the viscosity of the oil-based solvent. If the particle size of the metal soap is 5 μm or less, the metal soap can be used as a solid lubricant.
[0391] In the lubrication of oil well pipe threads, if the lubrication condition is poor, the lubricated part may generate heat, so the melting point of the solid lubricating film formed is preferably high. The melting point of the solid lubricating film is preferably 100° C. or higher, and the above preferred examples can meet this condition.
[0392] On the other hand, regarding alkaline soap (Na salt, K salt of fatty acid), even if it is not contained, it is preferred to actively add it with an upper limit of 1% or less. For water-based polymers, if alkaline soap is added, the viscosity of water increases and the drying time may become longer. In addition, it is difficult to apply and there is a possibility of uneven application. On the other hand, alkali metals improve lubrication properties. It acts as a solid lubricant itself, and the initial meshing position of the pin thread and the sleeve thread cannot be avoided in actual wells. Figure 5 However, when starting to tighten with a power tong, the soap effect guides the machine to slide into the proper meshing position, which helps improve the lubrication properties. As we experience in daily life, alkaline soap has a sliding viscosity when there is a small amount of moisture, so it is easy to achieve the above situation.
[0393] (Flash point)
[0394] The flash point of the reagent is 60° C. or higher, preferably 150° C., and it is preferably subjected to non-flammable treatment so that the flash point cannot be measured.
[0395] When restorative repairs are envisioned at a well site, it is possible to assume that the material is used in an environment where pyrotechnics are strictly prohibited. First, the ambient temperature for coating is assumed to be around -50°C to +50°C. Taking the margin into account, it can be assumed that the material is used at -60°C to +60°C. In addition, as the highest temperature of the current bottom of the well, 250°C is sometimes assumed as an exception, and as the highest temperature that can be envisioned as the well site temperature due to heat transfer, 150°C is sometimes assumed. Therefore, as described above, a temperature range is set. In order to make the risk level zero, the flash point cannot be measured and it is classified as non-flammable. This can be adjusted by the selection of lower alcohols and their blending ratios.
[0396] (Viscosity of coating agent and coating method)
[0397] The viscosity of the coating agent is preferably 1000 mPa·s or less.
[0398] Setting the viscosity of the reagent to be relatively low is one of the means for promoting early drying. In addition, the viscosity of the coating reagent is reduced in advance to increase fluidity, so that the film is achieved in a manner that the coating is not physically thick. As a means for achieving early drying, it is preferred to set the viscosity to less than 1000 mPa·second. It is also possible to try to make it thinner by treatments such as brushing. However, due to individual differences, it is preferred to adopt a method of reducing the viscosity of the liquid, increasing fluidity, and making it thinner. In addition, due to the low viscosity, the reagent easily enters the restorative local repair part, which is also effective for the repair of the buried part.
[0399] By this provision, it is possible to avoid an inadvertent thick film during coating. In addition, as a result, it can help early drying. The lower limit of the viscosity is not set, but it is about 40mPa·seconds or more. When a water-soluble or water-dispersible polymer material is added and mixed in an aqueous solution, the viscosity of water does not reach 1mPa·second. Due to the influence of the polymer material, there is a tendency for the viscosity to rise. Therefore, the level is about 40mPa·second. By making the viscosity of the coating agent less than 1000mPa·second, overlapping coating or surfacing becomes difficult. Accordingly, it has the advantage of being able to uniformly thin the thickness of the coating film. The adjustment of the viscosity is achieved by adjusting the amount of water, the selection of monomers constituting the water-based polymer, the concentration of the metal soap, the alkaline soap, and the mixing ratio containing the solvent.
[0400] On the other hand, the viscosity of the coating agent is less than 1000mPa·second, so the viscosity is small and it is easy to flow. The slower the drying, the more the coating agent in the dried part will sag. If the oil well pipe is coated horizontally, there is a tendency for the liquid to accumulate at the 6 o'clock position on the clock. This part has a tendency to accidentally become a thick film. Therefore, even if the 12 o'clock position is dried and filmed, there is a situation where only the accumulated 6 o'clock part does not dry in the above time. Therefore, it is preferred to use 0.1g / mm2 The coating is performed as follows. Furthermore, the coating amount is preferably within 30 minutes in a room temperature atmosphere environment and within 3 minutes in air drying with air flow of 1 m / s or more. This can be said to be a preferred range to avoid undrying at the 6 o'clock position.
[0401] The coating method of the reagent can be any method such as brushing, spraying, dipping, manual coating, mechanical coating, etc. It is also possible to take the following process: after actively and effectively utilizing the tendency of liquid dripping and coating, the object coated with the coating reagent is downward or tilted so that the coating flows downward. In addition, for the case where the coating object is a tubular object, it is preferred to apply it with bristles or spray while rotating compared to static coating. Thus, it is also possible to strengthen drying. Moreover, the surplus of the coating reagent that is not filmized is similarly applied to the metal surface again while rotating, which helps to form a uniform film. In addition, it is also possible to avoid accumulation at the 6 o'clock position.
[0402] (Local repair method and method of improving lubricity by coating an existing solid lubricating film)
[0403] The conditions for the coating agent were those specified in the above conditions.
[0404] When a slight burn occurs in the thread area of a threaded joint of an oil well pipe, the burned portion is cured using a grinder, a file, sandpaper, etc. After curing, the portion is repaired with a reagent to ensure lubrication again. Therefore, local repair can be performed by applying only the surrounding area or the entire surface including the burned portion. The oil well pipe threaded joint with the slight burn repaired in the thread area can be improved to be able to continue tightening and loosening more than once.
[0405] Alternatively, in order to improve the lubrication of other threaded joints of oil well pipes, the agent of the present invention may be applied to an existing solid lubricating film (which has not been tightened or loosened once). In this case, the lubrication characteristics can be improved compared to the case where the coating agent of the present invention is not applied, so that tightening and loosening can be performed more than once.
[0406] (As a film characteristic: film thickness)
[0407] It is preferred that the solid lubricating film formed using the coating agent has a film thickness of 10 μm to 100 μm, and the formed solid lubricating film is soft with a film hardness of B or less in pencil hardness.
[0408] The film thickness is the film thickness at the stage when the reagent dries and becomes a solid lubricating film. The film thickness is determined, for example, by observing each cross section obtained by cutting along the length direction at four locations along the circumferential direction of the threaded portion (for example, four locations every 90 degrees) with a microscope. Through this observation, the film thickness of the thickest part and the thinnest part of the film is determined. Then, it is confirmed whether each film thickness is within the above range.
[0409] It should be noted that, when the tendency of film thickness distribution is known based on past measurement results, the film thickness can also be estimated as follows. That is, if the coating / drying method of the reagent is the same, the maximum and minimum values of the film thickness of the entire threaded portion can be estimated by measuring the film thickness of a predetermined specific portion using an electromagnetic film thickness meter.
[0410] The meaning of film thickness is different in the case of forming a solid lubricating film using the reagent of the present invention during local repair and in the case of improving the lubrication of the entire surface by forming a solid lubricating film formed by the reagent of the present invention on a solid lubricating film that has not been tightened or loosened once. Here, the film thickness specified as a preferred range in the present invention: 10 μm or more and 100 μm or less means the following. That is, in the former case, it means the film thickness applied to the healthy part other than the damaged and partially repaired part. In the latter case, it means the film thickness indicating how much more is applied from the existing solid lubricating film. The thickness of the coating for the purpose of filling the part that has been restoratively ground away is excluded from the discussion of the film thickness.
[0411] Originally, as long as the uniform film thickness is about 10μm to about 50μm, lubrication is fully achieved. However, when a reagent with the above-mentioned viscosity is applied, due to the low viscosity, there is a tendency for the coating that cannot be film-formed to sag and move even if the drying is slightly strengthened or the coating amount is controlled to be low. Among them, the film thickness is defined as the thickness of the pliers (thread tooth part) together with the pin thread and the sleeve thread. This part is the only part that can be confirmed in a non-destructive manner, that is, the part that contacts the probe, so it is used as the film thickness measurement point.
[0412] Setting the lower limit to 10 μm or more is also related to the fact that the size of the graphite and metal soap of the solid lubricant is stipulated to be less than 5 μm. When the oil well pipe thread is tightened and loosened, when a load or torque is applied to the threaded portion, if it is less than 10 μm, the possibility of the solid lubricating film of the present invention being destroyed becomes higher. In addition, due to the absolute lack of film thickness, lubrication improvement is sometimes not achieved. The upper limit is set to less than 100 μm because, if it exceeds this range, on the contrary, compared with the role of assisting / improving lubrication, the possibility of the material that is ground into peeling pieces and powdery substances during tightening and loosening clogging the thread gap and promoting burns becomes higher. In the case of more than 100 μm, it is cut off during lubrication, and the peeling pieces tend to become the cause of burns. In addition, there is also the possibility of burning due to peeling without leaving any.
[0413] If the structure has threads such as the oil well pipe thread structure, there is an undeniable tendency for the coating agent to accumulate at the thread bottom, especially at the 6 o'clock position on a clock. In addition, due to the surface tension of the agent, there is also a tendency for the corner portion of the thread top of the thread structure to become thinner.
[0414] (As film property: pencil hardness)
[0415] The hardness of the formed solid lubricating film is preferably a pencil hardness of H or less.
[0416] This is because the solid lubricating film of the present invention is deliberately set to a soft film quality, and it is assumed that it is slightly ground when strongly touched, thereby achieving lubricating properties. The film is preferably soft with a pencil hardness of H or less. In the case of a high-hardness film exceeding H, when graphite or metal soap of a solid lubricant is added, it sometimes becomes brittle and detaches without leaving any due to the impact during tightening and loosening. Moreover, if they block the thread gap, the possibility of burns increases. It is preferably soft, and can be a pencil hardness of 2B or less, and more preferably a pencil hardness of 4B or less.
[0417] It should be noted that the film hardness is measured based on pencil hardness. The measurement method is measured according to the method specified in JIS K 5600-5-4 (1999). This standard is a translation of the "ISO / DIS 15184, Paints and varnishes-Determination of film hardness by pencil test" standard and is written in the JIS standard. The test method for pencil hardness of the present invention is evaluated based on the provisions of the JIS standard.
[0418] (Lubrication evaluation method)
[0419] The present invention is considered for the purpose of improving lubrication properties by restorative local repair and coating on an existing solid lubricating film (not tightened or loosened once).
[0420] When evaluating its characteristics, lubrication is evaluated under tightening and loosening conditions of oil well pipe threads along the tightening in actual wells. However, from the perspective of cost and experimental arrangement time, it is not realistic to evaluate the solid lubrication behavior of oil well pipe threads in actual wells or simulated wells.
[0421] As a new evaluation method for conditions close to actual well conditions, a weight of about 1 to about 3 pins of actual length is installed at the upper end of the short pin, and the initial setting position of the thread is set to a state where the pin thread is exposed about halfway relative to the sleeve thread. In addition, a weight is applied during tightening, and no weight is applied or the applied load is reduced during loosening to simulate tightening in an actual well. In addition, in this evaluation, the upper and lower limits of the parameters are determined according to the actual conditions. Hereinafter, the evaluation method including the application of the weight, the presence or absence of applied load (load ON during tightening, load OFF ~ reduced during loosening), and the initial placement position is collectively referred to as evaluation using a weight clamp.
[0422] The background is that if the evaluation using a horizontal power tong using a short pin of about 1m in length or the evaluation using a vertical power tong using a short pin is relied upon, the evaluation may be wrong. That is, in the "evaluation of the solid lubricating film" which is the object of the present invention, it may be wrongly evaluated as excellent. Therefore, the upper and lower limits of the parameters specified in the present invention become meaningless. The solid lubricating film is sometimes inevitably damaged when tightening and loosening. Therefore, the peeling pieces and powdery peeling materials do not always move in conjunction with tightening and loosening. Therefore, the peeling pieces block the thread gap and induce burns. However, in the evaluation using a short pin, since it is not easy to be damaged, it is possible to evaluate a sample that is originally bad as good. In addition, in the previous lubrication using a compound, since it is a viscous liquid compound, the compound moves in conjunction with tightening and loosening. Therefore, there is no big deviation between the evaluation results using a short pin and the evaluation in the actual well.
[0423] From the above, in the lubrication evaluation of the solid lubricating film, it is necessary to perform the evaluation by a new evaluation method designed so as to simulate an actual well.
[0424] It should be noted that in many past patent documents (in addition, the document numbers are not recorded in the present invention), in lubrication tests based on solid lubricating films, even in the case of large diameter sizes such as 9-5 / 8" and 13-3 / 8", it is often seen that the number of tightening and loosening can be up to 15-20 times. However, compared with grease-like compounds, this number is essentially impossible in solid lubricating films with poor lubrication properties. These are believed to be obtained by evaluation using short pins and horizontal or vertical power tongs, which are often observed in the laboratory. In this case, this characteristic is possible. However, in the tightening and loosening of actual wells, in the case of large-diameter oil well pipes using solid lubricating films, results at the level of 15 to 20 times are rare.
[0425] Based on the above considerations, in the evaluation method of the embodiment, by using Figure 6 and Figure 7 The simulation is to simulate the tightening and loosening test conditions that occur in an actual well or a simulated well. Figure 3 , Figure 5 The lubricity of the solid lubricant film was evaluated under the tightening conditions observed in the experiment.
[0426] What happens in actual wells is that, because the actual length of the pin is long, i.e., about 40 feet (≈ about 12 meters or more), it is impossible to "set the pin completely straight" during the initial setting. That is, the pin is almost always inserted at an angle. For the actual length of the pin thread, whether using a centering guide or using a compensator to try to set it straight, it is impossible to set it straight ideally. It is set at a very slight angle. In fact, the following situation will never happen: the pin thread is inserted into the sleeve thread, and the position that can be set by further tightening by manual tightening can be tightened to the point where the pin thread teeth are blocked by the sleeve thread. The thread teeth partially touch each other halfway, and no further progress will be made when the pin thread teeth are more than 5 teeth, or when about half of the total thread teeth are exposed. Figure 5 Therefore, at the beginning of tightening with pliers, rotate several times (in Figure 3 (a) is rotated about 6.3 turns) until the load increases, and then the pin thread and the sleeve thread begin to mesh at the correct position. In the oil well pipe thread, like many threaded structures, it has a tapered structure ( Figure 5 ). Therefore, the threads can finally be engaged in a stable position ( Figure 3 (b)). Figure 5As shown, if it is exaggerated, the part surrounded by the circle is severely damaged. That is, cracks, peeling, etc. are bound to occur at the microscopic level. The pin thread 1a is set slightly tilted. Therefore, due to the relationship with the thread rib 2a of the sleeve thread 2, there is a tendency for the position where the pin thread touches to be severely damaged at the front end of the pin thread 1a, near the middle of the thread rib of the thread rib 2a of the sleeve thread, and near the entrance of the thread rib 2a of the sleeve thread. Near the middle of the thread rib of the thread rib 2a of the sleeve thread refers to the vicinity of the position where the pin thread touches the sleeve thread when the pin thread is inserted and the vicinity of the center of the pin thread 1a. Near the entrance of the thread rib 2a of the sleeve thread refers to the vicinity of the entrance of the sleeve thread 2 when the pin thread is inserted.
[0427] Figure 3 In the process of measuring the torque of the screw thread, a spike-like torque rise is observed several times before reaching the stable position, that is, before the stable torque rise. This behavior directly causes the solid lubricating film to be damaged due to the uneven contact between the pin thread and the sleeve thread. In view of this, it is necessary to perform a lubrication evaluation of the solid lubricating film. The solid lubricating film is inevitably ground by the uneven contact between the threads. The peeling pieces and fragments do not necessarily move in conjunction with the tightening / loosening of the threads. Therefore, if the fragments are blocked in the thread gap, it becomes a major factor in burning.
[0428] The initial setting position of the pin thread cannot be set at the regular meshing position that theoretically meshes straight. Therefore, due to the looseness caused by this, the deadweight of the actual length pin, and their superposition, an uneven biased load is applied to the portion where the pin thread and the sleeve thread first contact. As a result of this large load / biased load, the solid lubricating film is inevitably peeled off or powdered. Moreover, they are blocked in the thread gap and burned. These effects are evaluated by a new method simulated in the laboratory. In the "solid lubricant composition composed of a metal soap containing a small amount of graphite" of the basic design of the present invention, the band-shaped secondary products caused by the presence of graphite are easy to block the thread gap when tightening and loosening. It is necessary to clarify the upper and lower limits of the parameters based on the simulation of this situation. If this is not done, the previous tests conducted in the laboratory using a short pin of about 1m using a horizontal power tong and a vertical power tong will become a mild condition test without applying the above-mentioned large load / biased load. As a result, in previous laboratory tests, even samples that failed in actual wells may be considered qualified. Therefore, the regulation of parameters becomes meaningless.
[0429] Figure 6 This is the overall concept diagram of the test method. Figure 7This is an enlarged view of the part involving the weight. In the weight tong test, a vertical power tong 4 is used. In addition, the short thread 1 and the sleeve thread 2 are tightened by the thread teeth of the pin thread part 1a and the thread teeth of the sleeve thread part 2a. At this time, in order to simulate the situation where the threads are not meshed, the initial temporary tightening position is set so that the pin thread part 1a appears to be exposed from the sleeve thread 2 by half of the total number of threads. This becomes one of the causes of loosening. Tightening is started from this state. At this time, a weight 3 is installed on the upper end of the pin 1 on the opposite side of the tightening thread. Regarding the weight of the weight 3, as a load equivalent to 1 to 3 actual length pins, the weight calculated based on the outer diameter and wall thickness of the pin is loaded. If it is 9-5 / 8" 53.5#, one pin is about 1 ton (2200Lb), and if it is equivalent to 3 connections, it is about 3 tons (6600Lb). Equivalent to 1 is an assumption of an onshore well, and equivalent to 3 is an assumption of tightening of an offshore well.
[0430] like Figure 7 As shown, in the weight 3, the insertion rod 13 is joined to the weight body 3A by welding at the axially symmetrical position of the weight. The insertion rod 13 is inserted into the pin 1, and the weight is installed on the upper end of the pin 1. Through holes 1d and 13a are pre-opened in the pin 1 and the insertion rod 13. In order to integrate the weight 3 with the pin 1, the through rod 12 is inserted into the through holes 1d and 13a. The swivel type hook 11 is fixed to the axial center position of the upper part of the weight 3 by welding, and is formed into a structure of a suspension device 20 suspended from the ceiling by a suspension chain 21. When tightening, the weight load is applied to the sleeve thread, and tightened at 5 to 20 rpm until the torque rises. The initial temporary tightening position and the high-speed rotation of tightening / loosening form a loose simulation. If the torque rises, the rotation speed is reduced to 0.5 to 2 rpm, and tightening is implemented to the tightening position.
[0431] As a simulation of the tightening and loosening test in the actual well, the load of the weight 3 may or may not be applied, especially when loosening the tightening. When loosening, it is preferred not to apply the load of the weight. If the loosening is carried out under the state of applying the load, the weight becomes a "weight" and a balancer when loosening from the tightening completion position, and is loosened in a manner that the pin thread rises straightly. That is, this is because it will not loosen, and when loosening, it will not damage the solid lubricating film. Even if the load is not set to zero, the test can be carried out by reducing the applied load by lifting the load. Including the case where the load is not completely zero, when the load is relaxed, the test can be carried out under conditions where the loosening is severe and there is a strong tendency to damage the solid lubricating film. Therefore, in the following evaluation, the weight is hung on it in a manner that the full load is applied when tightening and no load is applied when loosening, so that it becomes zero load~load reduction.
[0432] Regarding the rotation speed during loosening, when the torque increases, loosening is started at a rotation speed of 0.5 to 2 rpm, and when the torque reaches about 1 / 10 of the tightening torque value, loosening is performed at a high speed of 5 to 20 rpm. In this example, the evaluation is performed by the following method: when the loosening is completed, the pin thread and the sleeve thread are separated from each other by loosening, and the fragments from the solid lubricating film are scattered on each surface by blowing air, and the surface is inspected, and tightening is continued again.
[0433] The lubrication evaluation was performed by the above-mentioned method using a weight pliers and the following criteria were used to determine whether the lubrication was satisfactory.
[0434] In the case of restorative local repair, which will be described in detail later, a sample with intentional slight burns was prepared. Then, after the burnt part was ground with a grinder and paper for maintenance, a coating agent was applied. Then, it was determined whether more than one tightening and loosening was completed. The sample that was burned again was judged as a comparative example (NG), and the sample that could continue to tighten and loosen more than one to two times was set as a qualified judgment. The sample that could continue to tighten and loosen more than three times was set as a more excellent qualified judgment.
[0435] Regarding the judgment criteria for the case where the coating is applied to an existing solid lubricating film (not tightened or loosened once) to improve the lubrication characteristics, in the case of a film coated with a coating agent on the entire surface, the sample that can be tightened or loosened more than 1 to 2 times compared with the case without the film is judged as qualified. The sample that can be tightened or loosened more than 3 times is judged as a better qualified. The case without the coating agent and the sample with the same number of tightening and loosening or the number of tightening and loosening is judged as a comparative example (NG).
[0436] In addition to the number of times of tightening and loosening, after loosening, if it is completely loosened, let the pin come out upward, and observe the pin thread surface and sleeve thread surface after blowing air to directly check for burns. In addition, check the torque rotation diagram and judge based on whether there are any abnormal points.
[0437] (Method for simulating the occurrence of artificial burns)
[0438] In the present invention, in order to illustrate the effect of restorative local repair, artificial burns were formed as follows.
[0439] First, a special solid lubricating film for artificial burning is formed on the sleeve thread. Specifically, for the entire circumference of the sleeve thread, 1 / 8 of the circumference is masked with paper, and a reagent for the solid lubricating film is sprayed. Then, after temporary drying, it is fired to produce a sleeve thread with a special solid lubricating film. It should be noted that even if masking is performed, a broken wall-like structure with a film thickness of / without is not produced in the boundary area. At the masking boundary, the film thickness of the inevitable solid lubricating film gradually becomes thinner and becomes the formed film at the same time. On the other hand, the center of the masking (near the center observed from both ends of the paper masking) is in a state where the base film (Mn phosphate chemical conversion treatment film or electroplating film) is exposed. If tightening and loosening are performed in this state, only the masked part composed of the base Mn phosphate layer and the electroplating layer is burned, and the sample with good burn can be reproduced. In addition, when evaluating this sample, the heavy hammer clamp test method shown above is also used.
[0440] Example
[0441] Next, examples based on the present invention will be described.
[0442] (Example 1: Preparation method of metal soap)
[0443] In the research group of this Example 1, regarding the mixing method of the metal soap, the conditions were screened according to the mixing method with the liquid.
[0444] As the final basic composition of the coating agent, the weight ratio of the water-based polymer, the solid lubricant, and water is 40:20:40. Here, ethanol is mixed in a ratio of 1 to 100 weight of the total agent. In addition, a small amount of ammonia water is added for pH adjustment.
[0445] As a water-based polymer (binder resin), 10 parts by weight of acrylic acid was mixed with 100 parts by weight of vinyl acetate, and a copolymer of vinyl acetate and acrylic acid was used as a monomer. As a result, the polymer was 100% acrylic acid ester.
[0446] The solid lubricant used is a solid lubricant composed of metal soap and graphite, each of which has a particle size of 5 μm or less. At this time, the weight ratio of metal soap:graphite is set to 96:4. This means that the weight % of graphite is 4%. When preparing them, a substance in which each monomer of "copolymer of vinyl acetate and methacrylic acid" for forming an aqueous polymer is mixed in water is prepared, and metal soap and graphite are added to disperse them. In this embodiment, the contents of various studies on methods for uniformly dissolving metal soap and graphite in an aqueous polymer dissolved in a solvent mainly composed of water are shown. That is, the homogeneous dispersion in a series of studies in which mixing with industrial ethanol by the method shown below is investigated. In addition, as the metal soap described here, Ca stearate is used.
[0447] <Condition 1>
[0448] Condition 1 is an example where the metal soap and graphite are directly added to the base reagent according to the above-mentioned mixing ratio and stirred. This is an example where industrial ethanol is not used at all.
[0449] In condition 1, the metal soap and graphite were not mixed sufficiently and sometimes floated on the surface and aggregated with each other, so they could not be mixed well and uniformly. The results of condition 1 confirmed the conventional knowledge that these solid lubricants have water repellency and are insoluble in water.
[0450] <Condition 2>
[0451] Condition 2 is an example in which metal soap and graphite are added to the base reagent according to the above-mentioned mixing ratio and stirred, and industrial ethanol is added to the solvent composed of water at a volume / volume ratio of 2.5:100:100. This is equivalent to 1 part by weight when the final basic composition of the coating solvent "water-based polymer, solid lubricant, water" is set to 100 parts by weight. In this example, it was found that the metal soap and graphite were not fully mixed and floated on the surface and gathered together, so the metal soap and graphite could not be well mixed. Condition 2 shows that even if ethanol is added later, the metal soap and graphite cannot be well mixed.
[0452] <Condition 3>
[0453] Condition 3 is an example in which the amount of industrial ethanol is set to 2.5 relative to water:100, and the metal soap and graphite are stirred in industrial ethanol in another container, that is, uniformly mixed and then added to the base reagent and stirred. Condition 3 can be said to be an example of roughly homogeneous mixing. Metal soap and graphite are considered to be insoluble in water. However, in alcohol (industrial ethanol; ethanol is the main component), it is possible to achieve a state in which the particles of metal soap and graphite are finely dispersed without lumping together. Therefore, it can be seen that by temporarily dissolving the metal soap in industrial ethanol and then spreading and stirring the state in the base reagent, a state in which the metal soap and graphite are homogeneously dissolved can be formed.
[0454] <Condition 4>
[0455] In condition 4, the amount of industrial ethanol was 0.5 to 100: water, and metal soap and graphite were fully stirred in industrial ethanol in another container. However, although the amount of alcohol was small and the metal soap and graphite were dissolved, they were added to the base reagent in a state where they seemed to be unmixed. Condition 4 is an example in which industrial ethanol was added to the base reagent in an amount of 2: after the above, and stirred.
[0456] Condition 4 is an example where a substance previously dissolved in industrial alcohol can be prepared in an almost homogeneous manner when added to an aqueous solution. Furthermore, by adding only industrial ethanol:2 to the base reagent, dissolution proceeds further, and it can be recognized that homogeneous dispersion can be achieved.
[0457] <Condition 5>
[0458] In condition 5, the amount of industrial ethanol is 2 relative to 100 of water, and the metal soap and graphite are fully stirred in the industrial ethanol in another container and then added to the base reagent. Condition 5 is an example in which the amount of industrial ethanol 0.5 is added to the base reagent and stirred after the above. In this system, the metal soap Ca stearate and graphite are already in a state of being uniformly mixed in the industrial ethanol 2. Therefore, even if industrial ethanol is further added from this state, the metal soap Ca stearate does not change in particular, and it can be said that it is an example of uniform mixing.
[0459] From the above examples of conditions 1 to 5, it can be seen that a substance in which a suitable amount of metal soap and graphite are uniformly dissolved is temporarily prepared in advance with an appropriate amount of appropriate lower alcohol (an amount that can fully mix the metal soap). It can be seen that by putting it into the reagent body and stirring it, the metal soap can be mixed in a solvent with water as the main body. It should be noted that in the case of metal soap and graphite in an amount that cannot be uniformly mixed based on the volume of the lower alcohol, as long as they are not dissolved in advance in a lower ethanol of 0.5 or more relative to 100 water, only the graphite and metal soap are directly added to the basic reagent. It can be seen that even if additional industrial ethanol is added, the tendency of non-mixing becomes higher.
[0460] In addition, the following examples are based on the premise that the coating agent is a uniformly mixed metal soap.
[0461] (Example 2: Study on early drying property, coating amount, particle size of solid lubricant, drying method, etc.)
[0462] The study group of Example 2 is an example of applying the coating to the threads of oil well pipes and screening the good and bad parts by the drying condition.
[0463] In Example 2, the mixing ratio of alcohol to ammonia water, the type of alcohol, the size of metal soap and graphite were studied. Specifically, reagents with different conditions of the following reagents were systematically prepared and the early drying properties were examined.
[0464] The weight ratio of the water-based polymer, solid lubricant, water, and the addition amount of lower alcohol and ammonia water as other factors are expressed as weight ratios relative to water 100. It should be noted that ammonia water (concentrated ammonia water of about 28% to 30%) is added so as to achieve the pH range indicated for the water-based polymer.
[0465] The solid lubricant is composed of metal soap, alkaline soap and graphite. As the water-based polymer (binder resin), a copolymer prepared by mixing 100 parts by weight of acrylic acid with 6 parts by weight of polyvinyl alcohol as a monomer is used. The respective mixing ratios are systematically changed as shown in the research content of Example 2 for research. For example, polyvinyl alcohol is POVAL, which is a polyvinyl alcohol obtained by saponifying polyvinyl acetate obtained by polymerizing vinyl acetate monomer.
[0466] As a common experimental condition, the oil well pipe thread is made of carbon steel, L80 grade, 5.5” 23#, and JFEBEAR thread. TM Pin thread, oil well pipe thread with short strips of 700 to 1000 mm in length processed at both ends.
[0467] Regarding the method of applying the reagent, first, immerse a general paint brush (Japanese standard of bristles: No. 20: bristle width 50mm) in the coating reagent. Then, use two rollers to rotate the short pin the same number of times. In this case, the two rollers contact the 5.5" 23# pin thread at approximately the 5 o'clock and 7 o'clock positions on the clock. In addition, regard the pin thread of the object as an analog clock observed from the end face side, take the center position of the cross section as the center, set its upper position in the vertical direction to the 12 o'clock position, the lower position to the 6 o'clock position, the right position in the horizontal direction to the 3 o'clock position, and the left position to the 9 o'clock position. Under this condition, use a brush to apply while rotating the short pin at a speed of about 10 seconds per circle. Based on one coating, that is, set the bristles at the 12 o'clock position of the rotating tube. Then, from the pin thread The brush is brushed at a constant speed from the front end to the end of grinding the thread teeth, and only applied once. The coated part is the following part. That is, the end face of the entire thread area and the front end of the pin thread. Furthermore, it is a part about 10 mm inside. This part is inevitably coated due to the curling of the brush bristles. Moreover, it is a part of about 30 mm to about 50 mm in the area without thread teeth in the upper cut (crown part) of the thread teeth. This part is inevitably coated due to the curling of the brush bristles. 6 to 9 g is applied on one end. The coating amount is estimated by the change in the weight of the brush bristles. However, the part where the coating agent hangs down from the 6 o'clock position is not taken into account.
[0468] The two ends of the pin are grouped together. First, one side is coated as an example of drying in the atmosphere. Then, as an example of drying in the atmosphere, the other side is similarly coated while rotating, and is dried while being exposed to air at a flow rate of about 0.5 m / s in the atmospheric air supply mode of a manual dryer while continuing to rotate. Then, the drying time is recorded. Then, the rotation of the oil well pipe is stopped, and the drying time of the static drying side is also recorded. Touch it with your hand, and judge it as dry if there are no fingerprints left and it is not sticky.
[0469] The position for judging the drying is judged by the drying of the upper side of the oil well pipe and the position from 8 o'clock to 4 o'clock on the clock. In addition, the same judgment position is also set on the side where the drying is placed.
[0470] In the case of large-scale coating, the reagent accumulates at the static position and at the 6 o'clock position. However, it has solidified except for the extreme surface. Therefore, the judgment based on the fact that there is no problem from the perspective of the role played by the coating (lubrication) is used as the criterion for this judgment. In static drying, if 30 minutes cannot be considered dry, it is recorded as more than 30 minutes. In addition, the indoor temperature of the day was 25-28°C, and it was roughly this temperature during drying. Setting the forced drying condition to a simple air supply condition is a condition that dries slower and more stringent than the hot air delivery condition. However, if the drying condition is OK, it can be judged as qualified under any forced drying condition. This means that the research is conducted under the most stringent conditions imaginable.
[0471] In addition, the coating method based on the horizontal placement of the pin thread is used because the evaluation is performed under strict conditions compared to the vertical setting. In fact, in the local repair of restorative repair, the sleeve thread and the pin thread are vertically arranged. In this condition, the former is located at the upper part of the excavation hole of the well, and the latter is suspended on a crane. If a low-viscosity coating agent is applied, the excess coating component flows downward, so the coating will not accumulate. However, in the horizontal coating test, the coating agent is easy to accumulate, so the drying is easy to become strict. Therefore, the coating condition is set to the horizontal premise.
[0472] It should be noted that when mixing metal soap and graphite in the base reagent, the method "lower alcohol (ethanol: Example 1)" identified by the research group in Example 1 uses a method of mixing metal soap in advance and then mixing. The industrial ethanol mentioned here refers to high-purity ethanol, and methanol and isopropanol are mixed at a level that does not involve the liquor tax law. The alkaline soap is added and stirred at the final stage of the reagent preparation.
[0473] The coating weight is calculated from the weight difference of the bristles. However, since it contains volatile components, the part that only flies away cannot become a film-forming material, so it is difficult to say that it is the coating weight strictly speaking. However, in the present invention, the weight difference of the bristles is regarded as the coating weight for arrangement. However, since it is a coating agent with low viscosity and high fluidity, it is felt that a semi-dried coating is accumulated at the 6 o'clock position, especially on the side where it is placed after coating. Finally, there is also a part that drips from the 6 o'clock position, and its amount is a negligible coating amount. In addition, regarding the viscosity of the liquid, except for exceptions, a liquid of about 600 to 900 mPa·second and no major changes is prepared, and the influence of other conditions can be judged. The exception refers to an example equivalent to the following example: contrary to the case of increasing the solvent mixing ratio, that is, the coating agent mixed more dilutely in the aqueous solvent, an example of reducing water or increasing the amount of aqueous polymer to increase the viscosity is made.
[0474] The results and details of the conditions are shown in Tables 1 and 2.
[0475]
[0476]
[0477] The research cases No. 2-1 to 2-6 are cases where the early drying properties of water-based polymers composed of 6 parts by weight of polyvinyl alcohol were studied when the amount of acrylic acid was 100 parts by weight in a copolymer of acrylic acid and polyvinyl alcohol (POVAL; a substance obtained by saponifying polyvinyl acetate obtained by polymerizing vinyl acetate monomer). The viscosity of the coating agent is an example of using a low viscosity agent of 700 to 850 mPa·second. The mixing ratio of the water-based polymer, solid lubricant (metal soap and graphite), and water was 35:15:50, and ammonia was added only in a small amount for pH adjustment. In addition, this is an example of systematically changing the size of the metal soap and graphite, the type of alcohol, and the mixing ratio thereof for research. It should be noted that the films formed were 2B in pencil hardness, and their flash points were considered to be non-flammable in all cases. After the mixing of these, the alkaline soap was added at a weight ratio of 0.1 to the total weight of the solid lubricant: 15. Alkaline soap is soluble in water and tends to increase viscosity, which makes drying difficult. Therefore, in order to confirm the research on early drying under harsh conditions, it was added in this study. However, in the following description and Tables 2 and 3, its effect / influence is not specifically mentioned, and it exists as a common influencing factor.
[0478] No. 2-1 is a comparative example in which no metal soap, graphite, or alcohol is added. It serves as a benchmark for evaluating early drying. It is used to determine whether early drying is possible or whether the parameters other than early drying are satisfied.
[0479] No.2-2 is an example in which no metal soap or graphite is added to the solvent. That is, it is an example in which no metal soap or graphite is added. Since no graphite or metal soap is added for lubrication properties, it is treated as a comparative example. No.2-2 is an example in which the drying time is faster due to the volatilization of alcohol, but it does not exceed the target value of 5 minutes for air drying, and is a comparative example.
[0480] No.2-3 is a comparative example with metal soap, graphite and no alcohol. Metal soap and graphite are used to promote drying by increasing the surface area. However, since alcohol is not used, the metal soap tends to clump together. At the same time, the dissolution of graphite also tends to clump slightly. Even if the lubrication behavior is left aside, the reference conditions for drying time (air supply for less than 5 minutes and static drying for less than 30 minutes) cannot be met at the same time, so it is equivalent to a comparative example.
[0481] No.2-4 is an example with metal soap, no graphite, and alcohol. No.2-5 is an example with no metal soap, graphite, and alcohol. Although the drying time criterion is met, from the perspective of lubrication, the proportion of the solid lubricant is not within the specified range, so it is equivalent to a comparative example. The condition of No.2-5 with only graphite also meets the drying time criterion. There is a tendency for the drying time to be slightly faster. The reason is not clear, and it is possible that the tiny pore-like structure in the microstructure of the graphite plays a role. However, the proportion of the solid lubricant is not within the specified range of the present invention, and graphite alone cannot achieve lubrication characteristics, so it is treated as a comparative example (reference example).
[0482] No. 2-6 is an example of the present invention containing metal soap, graphite and alcohol, which shows that early drying can be achieved by designing the combination of solid lubricant, alcohol, ammonia and the like within the prescribed range of the present invention.
[0483] In addition, the examples of No. 2-7 to 2-18 are examples in which the water-based polymer is composed of a methacrylic acid-styrene copolymer. In addition, it is a copolymer with a mixing ratio of 9 parts by weight of styrene to 100 parts by weight of methacrylic acid. Since it is a copolymer, the binder resin component is treated as a 100% methacrylate. In addition, this example is an example of studying the type of soap, the type of alcohol, the concentration, etc. The viscosity of the coating agent is at the level of 350 to 550 mPa·second, which is an example of using a low-viscosity agent. In the examples of No. 2-7 to 2-18, the mixing ratio of the water-based polymer, the solid lubricant (metal soap and graphite), and water is 30:20:50. In addition, ammonia is added in a small amount for pH adjustment. In addition, it is an example of systematically changing the size of the metal soap and graphite, the type of alcohol, and the mixing ratio thereof to conduct research. In addition, the pencil hardness of the film formed by these is 4B. The flash point changes in conjunction with the amount of alcohol added.
[0484] No. 2-7 is the standard in which no metal soap, graphite, or alcohol is added.
[0485] In this regard, whether early drying is possible or whether the parameters other than early drying are satisfied becomes the criterion for judgment. No.2-8 to 2-9 are research examples in which the size of Ca stearate as the metal soap is changed. No.2-8 to 2-9 are all examples of the present invention that meet the criterion value for early drying. Compared with No.2-8, No.2-9 dries faster because the particle size of the metal soap and graphite is 1 μm, which is finer than the particle size of 5 μm of No.2-8, and the surface area increases, thereby promoting early drying.
[0486] No.2-10~11 are examples in which the amount of metal soap and the amount of industrial ethanol added are increased. No.2-10 is an example in which a larger amount of industrial ethanol is used to dissolve a substance equivalent to the upper limit of the amount of metal soap added in the invention example. No.2-10 has a fast drying time and meets the criteria for drying. However, due to the increase in ethanol, the flash point drops to about 60°C, but stops at the preferred lower limit of the flash point, which is equivalent to the present invention example. No.2-11 is an example in which the drying time is satisfactory but exceeds the preferred lower limit of the flash point and has a flash point in a low temperature range. There is no problem in using it unless it is an environment in which fireworks are strictly prohibited, but it is difficult to use in an environment in which fireworks are strictly prohibited at a well site, so it is positioned as a comparative example.
[0487] Examples No. 2-12 to 2-18 are examples in which various alcohols and metal soaps were studied. All of Examples No. 2-12 to 2-18 satisfy the goal of early drying, indicating that early drying is satisfactory within the prescribed range of the present invention.
[0488] (Example 3: Effect of various conditions on lubricity (local repair properties of repairability))
[0489] In the study group of Example 3, artificial burning was intentionally caused in the oil well pipe thread which has lubrication in the actual solid lubricating film. Then, in Example 3, the burned part was ground off with a grinder or sandpaper and cured. This is an example of applying the candidate coating agent studied in the present invention to the part to study lubrication.
[0490] The conditions are shown in Tables 3 and 4.
[0491] [Table 3]
[0492]
[0493] [Table 4]
[0494]
[0495] By combining the candidates of the sleeve thread side and the pin thread side of the solid lubricating film shown in Tables 3 and 4, a material having a lubricating film formed on the oil well pipe thread is prepared. However, when forming a solid lubricating film on the sleeve thread, a mask is applied by pasting paper at the inner angle of 30 degrees × 1 in the circumferential direction and over the entire thread portion to the entire length of the thread except for the sealing portion. Moreover, a solid lubricating film is not formed in this portion. Thus, a portion is intentionally made to expose the chemical conversion treatment film or electroplating film of the substrate. That is, paper or tape is added from 0 o'clock to 1 o'clock on the clock so that a solid lubricating film is not formed. There is a curled portion in the masked boundary area when the solid lubricating film is formed, so at the boundary, the presence or absence of the solid lubricating film cannot be clearly felt due to the curling of the reagent toward the sleeve thread.
[0496] In this state, the weight pliers are used to tighten and loosen once. As a result, approximately the same burn is achieved with the area of the dry film not masked as the center. The scope of the invention of the present invention is explained by making corrections to this. In addition, the test method of the weight pliers is in accordance with the above method. In addition, the repair (correction) of the burned area is carried out in a state where the weight pliers are set on the sleeve thread. That is, the weight pliers are set at the gripping part ( Figure 6 The reagent is applied by brushing after the part is cured with a grinder, file, or abrasive paper while the part is in the state of the lower gripping part of 4. The pin thread is also applied by brushing. Figure 7 As shown, the sleeve is hoisted to the upper part of the sleeve thread and the operation is performed from this state. Alternatively, the sleeve is hoisted by a crane and moved from just above the sleeve thread to a position slightly offset from the axis and the operation is performed at this position.
[0497] The case where the number of tightening and loosening increases by more than one time is treated as an invention example that can be repaired (≈corrected). When the next tightening and loosening test is performed, the sample that is burned again is judged by positioning it as a comparative example. The case where the number of tightening and loosening is completed more than three times after repair can be judged as more excellent. Tables 5 and 6 show the conditions and results of this embodiment.
[0498]
[0499]
[0500] In No.3-1 to 3-5, the oil well pipe is made of carbon steel Q125 material, 9-5 / 8” 53.5# size oil well pipe, and JFELION TM Thread. In addition, in No. 3-1 to 3-5, the solid lubricating film of the sleeve thread and the solid lubricating film of the pin thread correspond to 3-B2 and 3-P2 in Table 3 and Table 4, respectively. Then, the material in which artificial burning was caused was prepared. It should be noted that the evaluation was performed by tightening with a weight clamp by applying a load of 1 ton with a weight. That is, a load equivalent to the weight of a pin of actual length was applied.
[0501] Although there are some differences in degree, the solid lubricant film burns on the shielded sleeve thread and the corresponding pin thread after one tightening and loosening. The former burns in the shielded part (the part without the solid lubricant film), and when the pin thread burns, it burns in the friction part.
[0502] After the burn, the area was cured with a grinder, file, and abrasive paper, and then a coating agent was applied. The binder resin was a copolymer of vinyl acetate-butyl acrylate and polyethylene, and a material prepared by metal soap, graphite, alcohol, ammonia, etc. was applied, and tightened and loosened again.
[0503] No.3-1 to 3-2 are examples of restorative local repairs and further tightening and loosening three or more times using the reagents within the range specified by the present invention, which are equivalent to the present invention examples. In addition, the metal soap + graphite-based reagent does not form a band-shaped secondary product, fills the maintenance part with a film, and helps to restore high lubricity.
[0504] No. 3-3 is an example in which the size of graphite exceeds the preferred specification and is larger, and it can be improved to allow one more tightening and loosening. However, the improvement effect is not large. No. 3-4 is a comparative example in which the solid lubricant is excessive, that is, a large amount of graphite is added.
[0505] No.3-5, on the other hand, is an example of too little solid lubricant. They are all comparative examples of burning immediately after the local repair without improving the loosening of the tightening. In No.3-4, there is too much solid lubricant, that is, too much graphite, and the black belt-like secondary products are blocked in the thread gap and burn. In contrast, in No.3-5, the amount of lubricant component of the solid lubricating film is small, so it is believed that burning occurred due to insufficient lubrication.
[0506] Cases No. 3-6 to 3-10 are also made of carbon steel Q125 material, 9-5 / 8” 53.5# oil well pipe, using JFELION TM Thread. In the cases of No.3-6 to 3-10, the solid lubricating film of the sleeve thread and the solid lubricating film of the pin thread are different, which correspond to 3-B1 and 3-P1 in Table 3, respectively. It should be noted that the evaluation is to use a heavy hammer clamp to apply a 1-ton load to tighten and loosen. This means that a load equivalent to the weight of a pin of actual length is applied. The difference is that the coating agent is a copolymer film of polyethylene and acrylic acid.
[0507] No.3-6 to 3-7 are cases of reagents within the range specified by the present invention. Both are capable of restorative local repairs. The former is an example in which tightening and loosening can be further performed more than 3 times. The latter was improved only 2 times. Both belong to examples of the present invention. Graphite does not form a band-shaped secondary product, fills the maintenance part, and contributes to the restoration of high lubrication. It is presumed that the difference between No.3-6 and No.3-7 is caused by the difference in the size of the graphite. It is speculated that the small improvement effect of the latter is due to the deterioration of the clogging effect of the thread gap caused by the large graphite.
[0508] On the other hand, No. 3-8 is an example in which the proportion of solid lubricant is high. No. 3-9 is an example in which the proportion of water-based polymer is high. No. 3-10 is an example in which there is a lot of water. Nos. 3-8 to 3-10 are comparative examples in which the stability of the solid lubricating film is poor, the necessary lubrication cannot be ensured, and there is burning even after repair.
[0509] In cases No. 3-11 to 3-15, the material is stainless steel: UHP manufactured by JFE TM -15CR-125, 9-5 / 8” 47.0# oil well pipe, JFELION TM The object is the thread. In the examples of No.3-11 to 3-15, the solid lubricating film of the sleeve thread and the solid lubricating film of the pin thread are different, which correspond to 3-B3 and 3-P3 in Table 3, respectively. Moreover, materials for artificially causing burns were prepared in the same manner. It should be noted that the evaluation was carried out by tightening by applying a load of 2.5 tons using a heavy hammer pliers. This means that a load equivalent to the weight of 3 connected pins of actual length was applied. The water-based polymer is an ethylene-methacrylic acid copolymer resin (30:100). The ethylene mentioned here refers to the weight of ethylene polymerized with methacrylic acid using a random copolymer of ethylene oxide and propylene oxide.
[0510] No.3-11 to 3-12 are cases where the reagents within the range specified in the present invention were used. No.3-11 to 3-12 are cases where restorative local repairs can be performed and tightening and loosening can be performed more than three times, which are equivalent to the present invention examples. Graphite does not form a band-shaped secondary product, fills the maintenance part, and contributes to the recovery of high lubricity.
[0511] On the other hand, No.3-13 is an example of excessive graphite. Even if it is mixed with alcohol in advance and then added to the water-based paint, there is a tendency to form lumps, and it is a comparative example that is concerned about its influence. No.3-14 is an example in which no metal soap is added, which is equivalent to a comparative example. No.3-14 has not restored lubrication after repair. In other words, there is lubrication that cannot be achieved by a lubricant of graphite alone, and the results suggest that lubrication is achieved through their cooperation. On the contrary, No.3-15 is an example of a system without graphite and a system with only metal soap, which is equivalent to a comparative example. According to No.3-15, it is speculated that in the water-based solvent, even if alcohol is used to dissolve it in advance, the metal soap is not completely mixed, including forming lumps, and lubrication is insufficient.
[0512] (Example 4: Effects of various conditions observed from the perspective of lubricity (properties of overall lubricity improvement))
[0513] The examples of No. 4-1 to 4-5 of Example 4 are examples of two parallel comparative tests on the solid lubricating film used in the previous Example 3. One is to conduct only the tightening and loosening test to investigate the tightening and loosening times. It is the following method: on this basis, before tightening, the agent of the present invention is evenly applied to the surface, and a heavy hammer clamp test is conducted to investigate the tightening and loosening times, and whether there is improvement is understood based on the change in the number. This time, no burning is intentionally formed, but a uniform film is formed.
[0514] The results are shown in Tables 7 to 10.
[0515]
[0516]
[0517]
[0518]
[0519] Examples No. 4-1-B, 4-1-P, 4-1-BP, and 4-1-BP2 all used oil well pipe threaded pipes of the size and grade used in Examples No. 3-1 to 3-5. Moreover, it is a research example using the reagent of the conditions of No. 3-1 of Example 3 as a reagent that conforms to the present invention. In addition, the application of the reagent of the present invention as a lubrication aid applied on the existing solid lubricating film (3-B2, 3-P2 in Table 3) was observed. In No. 4-1-B, 4-1-P, 4-1-BP, and 4-1-BP2, the test was performed by a 1-ton weight tongs test.
[0520] Cases No. 4-1-B, 4-1-P, and 4-1-BP are examples where the reagent of the present invention is applied as a lubricating auxiliary agent to only the sleeve thread (internal thread), only the pin thread (external thread), and both the sleeve thread and the pin thread, respectively. Case No. 4-1-BP2 is an example where a solid lubricating film is formed on the pin thread surface using the reagent under the conditions of No. 3-1 of Example 3 instead of using a solid resin film formed by the reagent of 3-P2.
[0521] In the evaluation before forming the lubrication auxiliary film No.4-1-B, 4-1-P, and 4-1-BP, 7, 8, and 10 tightening and relaxing times were obtained. Moreover, when the reagent shown in No.3-1 of Example 3 was applied to the existing solid lubricating film, more than 10 tightening and relaxing times were achieved three times. Specifically, the test was stopped at 10 times. It can be seen that lubrication has been improved. In addition, in the heavy hammer clamp test with a load of 1 ton, there was no difference under these three conditions, and it can be seen that the lubrication behavior has been improved.
[0522] No.4-1-BP2 is a condition where the solid lubricating film 3-P2 on the pin thread side is replaced with the lubricating auxiliary film of the present invention. In this case, it is known that the lubricating auxiliary film also functions as the solid lubricating film itself on the pin thread side, and lubrication characteristics can be achieved.
[0523] In the case group No. 4-2-B, 4-1-P, and 4-1-BP, a test was conducted with a weight equivalent to three pins of actual length connected, using a 3-ton weight tong. These are examples of applying the reagent of the present invention as a lubricant auxiliary agent to only the sleeve thread (internal thread), only the pin thread (external thread), and both the sleeve thread and the pin thread. The three-pin connection condition is an example that simulates the conditions observed in the tightening of an offshore platform. In the evaluation before the improvement of the lubricating film, the number of tightening and loosening was 3 times, 5 times, and 5 times. In contrast, when the agent shown in No. 4-2 (same as No. 4-1-B, 4-1-P, 4-1-BP, 4-1-BP2) was applied as an improvement in lubrication behavior and lubrication assistance, the number of tightening and loosening times was in the order of No. 4-2-B, 4-1-P, 4-1-BP, such as "≥10 times, ≥10 times, ≥10 times", "≥10 times, 8 times, ≥10 times", "7 times, 8 times, 8 times", and so on. The lubrication improvement effect of No. 4-2-B and 4-1-P only for the sleeve thread and only for the pin thread is better than the condition of applying to both the sleeve thread and the pin thread. By applying to both, the amount of lubrication auxiliary film applied is about doubled. Therefore, it is estimated that even if the solid lubricating film is ground into powder or fragments during tightening and loosening, it is easy to clog the gap of the thread and burn it because it increases. All are comparisons of good and bad within the acceptable range.
[0524] The same result was obtained in the case of No. 4-3-B. That is, it was found that lubrication was improved by forming a top coating layer applied on the sleeve thread side in anticipation of a lubrication assisting effect by the coating agent within the prescribed range.
[0525] Cases No. 4-4-B-0, 4-4-B-0.5, 4-4-B-1.0, 4-4-B-3.0, 4-4-B-5.0, and 4-4-B-8.0 are examples where the lubrication assisting effect is expected on the sleeve thread side by applying the coating agent within the specified range. These cases are the results of comparative research and investigation of the graphite content under the conditions where the addition amount of graphite relative to the total weight of the solid lubricant is 0.0%, 0.5%, 1.0%, 3.0%, 5.0%, and 8.0%, respectively.
[0526] Without adding graphite, there is no lubrication improvement effect, but when it contains 0.5-5.0%, it has a lubrication improvement effect. In particular, in the range of 1.0-3.0%, an excellent lubrication improvement effect is clearly shown. On the other hand, in the case of 8.0% exceeding 5.0%, deterioration of lubrication properties is observed. In this way, the graphite blending in an appropriate range is the key to achieving excellent lubrication behavior.
[0527] In the case of No.4-5-B, even without lubrication support, the evaluation results have achieved ≥10 tightening and loosening times in three attempts, so the improvement cannot be evaluated. However, from the cases of No.4-1 to 4-4, it can be inferred that under more stringent lubrication conditions, there are many improvements.
[0528] (other)
[0529] The present invention can also adopt the following configurations.
[0530] (1) A coating agent for forming a solid lubricating film by coating on a metal surface, wherein:
[0531] The coating agent contains a solid lubricant, a binder resin and a solvent as main components.
[0532] The solvent contains water as a main component, and a lower alcohol having a carbon number of 3 or less is added to the water as an additive, wherein the volume of the additive is 0.5 or more and 10 or less relative to 100 of the volume of the water.
[0533] More than 95% of the volume of the solvent is composed of the water and the additives.
[0534] As the above-mentioned solid lubricant, graphite and metal soap are contained in an amount of 95% or more by weight of the total solid lubricant components.
[0535] As the solid lubricant, the solid lubricant further contains an alkaline soap in an amount of 0% to 1% by weight of the total solid lubricant component.
[0536] The graphite accounts for 0.5% to 5% by weight of the entire solid lubricant.
[0537] The binder resin is a water-soluble or water-dispersible polymer, and the polymer is a polymer or copolymer containing 90% or more of a monomer belonging to acrylate or methacrylate based on the total weight of the binder resin.
[0538] (2) Ammonia water is also added as the above-mentioned additive.
[0539] (3) the binder resin accounts for 30% to 40% of the total weight of the reagent,
[0540] The solid lubricant accounts for 10% to 20% of the total weight of the reagent.
[0541] The solvent accounts for 40% to 50% of the total weight of the reagent.
[0542] (4) as a solvent component, at least one of the lower alcohols in the lower alcohol and ammonia water is added as an additive to the water constituting the above-mentioned solvent, wherein the above-mentioned lower alcohol contains one or two or more lower alcohols having a carbon number of 3 or less,
[0543] The volume of the lower alcohol is 0.5 or more and 10 or less relative to 100 of the volume of water constituting the solvent,
[0544] The volume of the ammonia water is 0 or more and 5 or less relative to 100 of the volume of water constituting the solvent.
[0545] (5) The above-mentioned lower alcohol is a lower alcohol selected from methanol, ethanol, isopropanol, n-propanol and industrial ethanol.
[0546] (6) The average particle size of the graphite is 5 μm or less,
[0547] The average particle size of the metal soap is 5 μm or less.
[0548] (7) The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of a monomer selected from the monomers described in (1) to (4) below, or a copolymer comprising two or more monomers selected from the monomers described in (1) to (4) below,
[0549] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0550] (2) Monomers that integrate acrylic acid esters, methacrylic acid esters, and their derivatives with monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters, and their derivatives;
[0551] (3) A monomer grafted with the above (1) or (2);
[0552] (4) A monomer composed of one or both of a vinyl compound and a carbamate compound and at least one of the monomers (1) to (3) integrated together
[0553] (8) The metal soap comprises one or more metal soaps, wherein the metal soap is a compound formed of a fatty acid selected from the following group A and a metal element selected from the following group B,
[0554] The alkaline soap includes one or more alkaline soaps, wherein the alkaline soap is a compound formed of a fatty acid selected from the following group A and a metal element selected from the following group C.
[0555] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0556] Group B: Mg, Ca, Zn, Ba;
[0557] Group C: Na, K.
[0558] (9) The coating agent of the present invention has a flash point of 60° C. or higher, or is non-flammable.
[0559] (10) The coating agent of the present invention, wherein the viscosity of the agent is 1000 mPa·s or less.
[0560] (11) With a 0.1g / mm 2 When the following coating amount is applied and left to dry in a normal temperature atmosphere, the product has an early drying property that allows it to dry within 30 minutes.
[0561] (12) With a 0.1g / mm 2 The following coating amounts are applied and dried with air blowing at 1 m / s or more in a normal temperature atmosphere, and the early drying property is achieved that the product dries within 3 minutes.
[0562] (13) The method for producing a coating agent of the present invention comprises preparing the metal soap by dispersing the metal soap in the lower alcohol to make it turbid and then adding the dispersed metal soap into water as a solvent.
[0563] (14) A method for repairing a lubricating film on a threaded portion of an oil well pipe, comprising curing a burned region of the threaded portion of the oil well pipe and then applying the coating agent of the present invention to at least the cured region.
[0564] (15) With respect to an oil country tubular good having a solid lubricating film formed on a threaded portion, the coating agent of the present invention is applied onto the solid lubricating film.
[0565] (16) An oil country pipe having a lubricating film having a solid lubricating film formed on a threaded portion, wherein:
[0566] The solid lubricating film is formed by dispersing a solid lubricant in a binder resin.
[0567] As the solid lubricant, graphite and metal soap account for 95% or more of the weight of the total solid lubricant component.
[0568] As the solid lubricant, the solid lubricant further contains an alkaline soap in an amount of 0% to 1% by weight of the total solid lubricant component.
[0569] The graphite accounts for 0.5% to 5% by weight of the entire solid lubricant.
[0570] The binder resin is a water-soluble or water-dispersible polymer, and the polymer is a polymer or copolymer containing 90% or more of a monomer belonging to acrylate or methacrylate based on the total weight of the binder resin.
[0571] (17) The average particle size of the graphite is 5 μm or less,
[0572] The average particle size of the metal soap is 5 μm or less.
[0573] (18) The metal soap accounts for 0.5% to 5% by weight of the entire solid lubricant.
[0574] (19) The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of a monomer selected from the monomers listed in (1) to (4) below, or a copolymer comprising two or more monomers selected from the monomers listed in (1) to (4) below,
[0575] (1) Monomers mainly composed of acrylate, methacrylate and their derivatives;
[0576] (2) Monomers that integrate acrylic acid esters, methacrylic acid esters, and their derivatives with monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters, and their derivatives;
[0577] (3) A monomer grafted with the above (1) or (2);
[0578] (4) A monomer composed of one or both of a vinyl compound and a urethane compound and at least one of the monomers (1) to (3) integrated together.
[0579] (20) The metal soap comprises one or more metal soaps, wherein the metal soap is a compound formed of a fatty acid selected from the following group A and a metal element selected from the following group B,
[0580] The alkaline soap includes one or more alkaline soaps, wherein the alkaline soap is a compound formed of a fatty acid selected from the following group A and a metal element selected from the following group C.
[0581] Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid;
[0582] Group B: Mg, Ca, Zn, Ba;
[0583] Group C: Na, K.
[0584] (21) The solid lubricating film has a thickness of 10 μm or more and 100 μm or less, and is soft with a film hardness of B or less in pencil hardness.
[0585] The entire contents of Japanese Patent Application No. 2022-134376 (filed on August 25, 2022) to which this application claims priority are incorporated herein by reference. Although the invention is described with reference to a limited number of embodiments, the scope of the invention is not limited thereto, and changes based on the above disclosed embodiments are obvious to those skilled in the art.
[0586] Explanation of symbols
[0587] 1 Pin
[0588] 1a Threaded part
[0589] 2 Sleeve
[0590] 2a Threaded part
Claims
1. A coating agent for forming a solid lubricating film, which is a coating agent for forming a solid lubricating film by coating on a metal surface, wherein: The coating agent contains a solid lubricant, a binder resin and a solvent as main components. The solvent contains water as a main component, and a lower alcohol having a carbon number of 3 or less is added to the water as an additive, wherein the volume of the additive is 0.5 or more and 10 or less relative to the volume of 100 of the water, More than 95% of the volume of the solvent is composed of the water and the additive, As the solid lubricant, the solid lubricant contains graphite and metal soap which account for more than 95% of the weight of the total solid lubricant components. The solid lubricant further contains an alkaline soap in an amount of 0% to 1% by weight of the total solid lubricant component. The graphite accounts for 0.5% to 5% of the total solid lubricant by weight. The binder resin is a water-soluble or water-dispersible polymer, and the polymer is a polymer or copolymer containing 90% or more of a monomer belonging to acrylate or methacrylate in terms of the total weight of the binder resin.
2. The coating agent for forming a solid lubricating film according to claim 1, wherein Ammonia water was also added as the additive.
3. The coating agent for forming a solid lubricating film according to claim 1 or claim 2, wherein: The binder resin accounts for 30% to 40% of the total weight of the reagent. The solid lubricant accounts for more than 10% and less than 20% of the total weight of the reagent, The solvent accounts for more than 40% and less than 50% of the total weight of the reagent.
4. The coating agent for forming a solid lubricating film according to any one of claims 1 to 3, wherein As a solvent component, at least a lower alcohol in a lower alcohol and ammonia water is added as an additive to the water constituting the solvent, wherein the lower alcohol includes one or two or more lower alcohols having a carbon number of 3 or less, The volume of the lower alcohol is 0.5 or more and 10 or less relative to 100 of the volume of water constituting the solvent, The volume of the ammonia water is greater than or equal to 0 and less than or equal to 5 with respect to 100 of the volume of water constituting the solvent.
5. The coating agent for forming a solid lubricating film according to any one of claims 1 to 4, wherein The lower alcohol is selected from methanol, ethanol, isopropanol, n-propanol and industrial ethanol.
6. The coating agent for forming a solid lubricating film according to any one of claims 1 to 5, wherein The average particle size of the graphite is less than 5 μm, The average particle size of the metal soap is 5 μm or less.
7. The coating agent for forming a solid lubricating film according to any one of claims 1 to 6, wherein The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of a monomer selected from the monomers described in (1) to (4) below, or a copolymer comprising two or more monomers selected from the monomers described in (1) to (4) below. (1) Monomers mainly composed of acrylate, methacrylate and their derivatives; (2) Monomers that integrate acrylic acid esters, methacrylic acid esters, and their derivatives with monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters, and their derivatives; (3) a monomer grafted with (1) or (2); (4) A monomer composed of one or both of a vinyl compound and a urethane compound and at least one of the monomers (1) to (3) integrated together.
8. The coating agent for forming a solid lubricating film according to any one of claims 1 to 7, wherein As the metal soap, one or more metal soaps are included, and the metal soap is a compound formed by a fatty acid selected from the following group A and a metal element selected from the following group B, As the alkaline soap, one or more alkaline soaps are included, and the alkaline soap is a compound formed by a fatty acid selected from the following group A and a metal element selected from the following group C, Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid; Group B: Mg, Ca, Zn, Ba; Group C: Na, K.
9. The coating agent for forming a solid lubricating film according to any one of claims 1 to 8, wherein The reagent has a flash point of 60°C or higher, or is non-flammable.
10. The coating agent for forming a solid lubricating film according to any one of claims 1 to 9, wherein The viscosity of the reagent is 1000 mPa·s or less.
11. The coating agent for forming a solid lubricating film according to any one of claims 1 to 10, which has a coating agent having a strength of 0.1 g / mm on a metal surface. 2 When the following coating amount is applied and left to dry in a normal temperature atmosphere, the product has an early drying property that allows it to dry within 30 minutes.
12. The coating agent for forming a solid lubricating film according to any one of claims 1 to 11, which has a coating strength of 0.1 g / mm on a metal surface. 2 The following coating amounts are applied and dried with air blowing at 1 m / s or more in a normal temperature atmosphere, and the early drying property is achieved that the product dries within 3 minutes.
13. A method for producing a coating agent for forming a solid lubricating film, which is the method for producing a coating agent according to any one of claims 1 to 12, wherein: The metal soap is prepared by dispersing the metal soap in the lower alcohol to make it turbid and then adding the metal soap into water as a solvent.
14. A method for repairing an oil well pipe, which is a method for repairing a lubricating film on a threaded portion of an oil well pipe, wherein: After curing the burned area in the threaded portion of the oil country pipe, the coating agent for forming a solid lubricating film according to any one of claims 1 to 12 is applied to at least the cured portion.
15. A method for improving lubrication of oil well pipes, wherein: In an oil country tubular good having a solid lubricating film formed on a threaded portion, the coating agent for forming a solid lubricating film according to any one of claims 1 to 12 is applied to the solid lubricating film.
16. An oil country pipe having a lubricating film having a solid lubricating film formed on a threaded portion, wherein: The solid lubricating film is formed by dispersing a solid lubricant in a binder resin. As the solid lubricant, graphite and metal soap account for 95% or more of the weight of the entire solid lubricant component. The solid lubricant further contains an alkaline soap in an amount of 0% to 1% by weight of the total solid lubricant component. The graphite accounts for 0.5% to 5% of the total solid lubricant by weight. The binder resin is a water-soluble or water-dispersible polymer, and the polymer is a polymer or copolymer containing 90% or more of a monomer belonging to acrylate or methacrylate in terms of the total weight of the binder resin.
17. The oil well pipe according to claim 16, wherein: The average particle size of the graphite is less than 5 μm, The average particle size of the metal soap is 5 μm or less.
18. The oil well pipe according to claim 16 or claim 17, wherein: The metal soap accounts for 0.5% to 5% by weight of the entire solid lubricant.
19. The oil country pipe according to any one of claims 16 to 18, wherein: The water-soluble or water-dispersible polymer constituting the binder resin is a polymer composed of a monomer selected from the monomers described in (1) to (4) below, or a copolymer comprising two or more monomers selected from the monomers described in (1) to (4) below. (1) Monomers mainly composed of acrylate, methacrylate and their derivatives; (2) Monomers that integrate acrylic acid esters, methacrylic acid esters, and their derivatives with monomers containing alkyl esters, vinyl esters, styrene esters, carboxylic acid esters, and their derivatives; (3) a monomer grafted with (1) or (2); (4) A monomer composed of one or both of a vinyl compound and a urethane compound and at least one of the monomers (1) to (3) integrated together.
20. The oil country pipe according to any one of claims 16 to 19, wherein As the metal soap, one or more metal soaps are included, and the metal soap is a compound formed by a fatty acid selected from the following group A and a metal element selected from the following group B, As the alkaline soap, one or more alkaline soaps are included, and the alkaline soap is a compound formed by a fatty acid selected from the following group A and a metal element selected from the following group C, Group A: stearic acid, behenic acid, lauric acid, 12-hydroxystearic acid, oleic acid, montanic acid; Group B: Mg, Ca, Zn, Ba; Group C: Na, K.
21. The oil country pipe according to any one of claims 16 to 19, wherein The solid lubricating film has a film thickness of 10 μm or more and 100 μm or less, and is soft with a film hardness of B or less in pencil hardness.
Citation Information
Patent Citations
Shoulder patter
JP1982022752A
Screw joint for steel pipe
JP2002327874A
Thread coupling for steel pipes
JP2004053013A
Threaded fittings for steel pipes
JP2008527249A
Threaded joints for steel pipes
JP2008537062A